Curable composition for forming adhesive structure, adhesive structure, method for manufacturing adhesive structure, and semiconductor device

By using an inkjet printing method to eject a curable composition containing a glycidyl amine type epoxy compound, an oxetane compound and a cationic polymerization initiator on an electronic circuit substrate, the existing technology problems of heat resistance, thinness and Solve the problems of insufficient integration and reliability and realize highly integrated and high-speed semiconductor packaging.

CN119343423APending Publication Date: 2025-01-21RICOH CO LTD

Patent Information

Application Number
CN202380045101.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-19
Filing Date
2023-06-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to achieve heat resistance, thinner and high reliability chip bonding components in highly integrated and high-speed electronic circuit substrates, especially when semiconductor heat generation increases.

Method used

An inkjet printing method is used to discharge a curable composition, which includes a glycidyl amine type epoxy compound, an oxetane compound and a cationic polymerization initiator, and the ratio of the glycidyl amine type epoxy compound is 10 mass %above.

Benefits of technology

It achieves the formation of an adhesive structure with excellent heat resistance and flexibility, which can maintain the adhesive function at high temperatures, reduce thermal stress, and improve the thinness and reliability of semiconductor packages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005171347690000061
    Figure BDA0005171347690000061
  • Figure BDA0005171347690000062
    Figure BDA0005171347690000062
  • Figure BDA0005171347690000071
    Figure BDA0005171347690000071
Patent Text Reader

Abstract

Provided is a curable composition for forming an adhesive structure, which can be discharged by an inkjet printing method, and which comprises a glycidyl amine type epoxy compound, an oxetane compound, and a cationic polymerization initiator. The ratio of the glycidyl amine type epoxy compound in the curable composition is 10% by mass or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable composition for forming an adhesive structure, an adhesive structure, a method for producing an adhesive structure, and a semiconductor device. Background Art

[0002] In electronic circuit substrates, along with high integration and high speed, the temperature rise caused by heating elements such as IC chips increases, and there is a requirement for heat-resistant reliability of bonding and connection of installed circuits. As the main reason for the reduction of bonding and connection reliability, thermal stress caused by the difference in linear thermal expansion coefficients between the semiconductor (chip) and the various materials bonded to the semiconductor (chip) can be cited. Specifically, the linear thermal expansion coefficient of the semiconductor (chip) is about 3ppm / K, while the linear thermal expansion coefficient of the mounting substrate is as large as more than 15ppm / K. Therefore, thermal stress is generated due to thermal cycles caused by heating production process steps such as reflow and drive heating, which makes it easy for poor bonding and connection of the semiconductor (chip) to occur.

[0003] In the past, as chip bonding components for bonding chips to each other and chips to substrates, solution-based chip bonding pastes and sheet-like chip bonding films were used. Due to the increased heat generation of highly integrated chips and the thinning of devices such as smartphones, these chip bonding components are required to have high heat resistance and thinness. On the other hand, it is known that the thickness of the device can be reduced by forming the adhesive portion into a thin film, and the heat dissipation effect of the heating mold can be obtained. As a method for forming a thin film of a chip bonding component with uniform thickness, a method of applying a curable resin composition as a chip bonding component by inkjet printing is proposed (see Patent Document 1, Patent Document 2).

[0004] Citation list

[0005] Patent Literature

[0006] [Patent Literature]

[0007] [Patent Document 1] Japanese Unexamined Patent Application Publication No. 2018-065957

[0008] [Patent Document 2] Japanese Unexamined Patent Application Publication No. 2014-237814 Summary of the invention

[0009] Technical issues

[0010] An object of the present invention is to provide a curable composition for forming an adhesive structure which can form an adhesive structure having excellent adhesiveness, heat resistance and flexibility.

[0011] Solutions to the problem

[0012] The curable composition for forming an adhesive structure of this embodiment, which is a solution to the above-mentioned problem, can be discharged by inkjet printing, and the curable composition includes: a glycidylamine type epoxy compound; an oxetane compound; and a cationic polymerization initiator, and the proportion of the glycidylamine type epoxy compound in the curable composition is 10% by mass or more.

[0013] Effects of the Invention

[0014] According to the present invention, there can be provided a curable composition for forming an adhesive structure capable of forming an adhesive structure having excellent adhesiveness, heat resistance and flexibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] A more complete understanding of the embodiments and many of the attendant advantages and features thereof can be readily obtained and understood from the following detailed description taken in conjunction with the accompanying drawings.

[0016] [ Figure 1A ]

[0017] Figure 1A It is a schematic cross-sectional view in the film thickness direction of an example of the adhesive structure of this embodiment.

[0018] [ Figure 1B ]

[0019] Figure 1B This is a schematic diagram of an example of the pressure-sensitive adhesive structure of the present embodiment as viewed from above the pressure-sensitive adhesive layer.

[0020] [ Figure 2A ]

[0021] Figure 2A It is a schematic cross-sectional view in the film thickness direction of another example of the adhesive structure of the present embodiment.

[0022] [ Figure 2B ]

[0023] Figure 2B This is a schematic diagram of another example of the adhesive structure of the present embodiment as viewed from above the adhesive layer.

[0024] [ Figure 3A ]

[0025] Figure 3A It is a schematic cross-sectional view in the film thickness direction of another example of the adhesive structure of the present embodiment.

[0026] [ Figure 3B ]

[0027] Figure 3B This is a schematic diagram of another example of the adhesive structure of the present embodiment as viewed from above the adhesive layer.

[0028] [ Figure 4 ]

[0029] Figure 4 This is a schematic cross-sectional view of an example of the semiconductor device according to this embodiment.

[0030] [ Figure 5 ]

[0031] Figure 5 This is a schematic cross-sectional view of another example of the semiconductor device according to this embodiment.

[0032] [ Fig. 6A ]

[0033] Fig. 6A This is a schematic cross-sectional view of another example of the semiconductor device according to this embodiment.

[0034] [ Figure 6B ]

[0035] Figure 6B This is a schematic cross-sectional view of another example of the semiconductor device according to this embodiment.

[0036] [ Fig. 7A ]

[0037] Fig. 7A This is a schematic cross-sectional view of another example of the semiconductor device according to this embodiment.

[0038] [ Figure 7B ]

[0039] Figure 7B This is a schematic cross-sectional view of another example of the semiconductor device according to this embodiment.

[0040] [ Fig. 8A ]

[0041] Fig. 8A This is a schematic cross-sectional view of another example of the semiconductor device according to this embodiment.

[0042] [ Figure 8B ]

[0043] Figure 8B This is a schematic cross-sectional view of another example of the semiconductor device according to this embodiment.

[0044] [ Fig. 9 ]

[0045] Fig. 9 This is a schematic cross-sectional view of another example of the semiconductor device according to this embodiment.

[0046] The accompanying drawings are intended to describe embodiments of the present disclosure and should not be interpreted as limiting the scope thereof. Unless explicitly noted, the accompanying drawings should not be considered to be drawn to scale. Moreover, throughout the several views, the same or similar reference numerals represent the same or similar components. DETAILED DESCRIPTION

[0047] In describing the embodiments shown in the drawings, specific terms are used for clarity. However, the disclosure of this specification is not intended to be limited to the specific terms selected, and it should be understood that each specific component includes all technical equivalents having similar functions, operating in a similar manner and achieving similar results.

[0048] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0049] (Curable composition for forming adhesive structure)

[0050] The adhesive structure-forming curable composition of the present embodiment is a curable composition for forming an adhesive structure that can be ejected by inkjet printing, and contains a glycidylamine epoxy compound, an oxetane compound, and a cationic polymerization initiator. The proportion of the glycidylamine epoxy compound in the curable composition is 10% by mass or more. The adhesive structure-forming curable composition further contains other components as needed.

[0051] In the prior art (for example, Patent Document 1), a curable resin composition for use in an inkjet method is proposed. The curable resin composition contains an acrylonitrile copolymer (rubber) that imparts flexibility in addition to an alicyclic epoxy monomer.

[0052] In such existing curable resin compositions, in order to reduce the viscosity of the curable resin compositions, low molecular weight alicyclic epoxy monomers are used. However, it is difficult to satisfy the characteristics of curing performance and cured products by using only low molecular weight alicyclic epoxy monomers. Specifically, the curing reaction of alicyclic epoxy monomers is fast, and the glass transition temperature (Tg) of the cured products of alicyclic epoxy monomers is high, so the heat resistance is excellent. However, the elastic modulus of the cured product is high, so the cured product has the disadvantages of being hard and brittle. Generally, the viscosity of acrylonitrile copolymers (rubbers) is high. If acrylonitrile copolymers are added in large quantities, the viscosity of the resulting product becomes high, and therefore, there is a tendency that the effect of imparting flexibility is insufficient, and in addition, there is a problem that ink materials and mixing ratios are restricted.

[0053] On the other hand, non-alicyclic epoxy monomers (e.g., glycidyl ether epoxy monomers) impart excellent flexibility to cured products, but have the disadvantages of slow curing reaction and low glass transition temperature (Tg). Therefore, if the curable resin composition used as a chip bonding component is a single material, it is difficult to cope with the increase in heat generation of the semiconductor and to achieve a thinner semiconductor package.

[0054] In the prior art (eg, Patent Document 1), it has been proposed to use ink having a high viscosity at room temperature (25° C.) and heat the ink to a temperature of 50° C. or higher to reduce the viscosity, thereby adjusting the viscosity to a viscosity suitable for an inkjet system.

[0055] However, when the thermosetting ink is heated to a high temperature, the ink easily solidifies and forms a gel, so that the ink cannot be used in an inkjet printing device for a long time. In addition, the solidification of the ink may cause clogging of the fine nozzle holes of the inkjet system.

[0056] The curable composition for forming an adhesive structure of the present embodiment contains a glycidylamine epoxy compound, an oxetane compound and a cationic polymerization initiator, and the proportion of the glycidylamine epoxy compound in the curable composition is 10% by mass or more. Thus, the adhesive structure as a cured product of the curable composition for forming an adhesive structure can be given excellent adhesive properties of heat resistance and flexibility. In addition, the curable composition for forming an adhesive structure of the present embodiment is not easy to evaporate when heated, and is stable even when heated, and the volume reduction of the cured product is small.

[0057] Hereinafter, the adhesive structure of the present invention is formed with a curable composition for explanation. The present invention is not limited to the embodiments described below, but may be other embodiments, and within the scope that can be expected by a person skilled in the art, changes such as addition, change, and omission may be made. As long as these deformation modes can bring into play the effect of the present invention, they are all included in the scope of the present invention.

[0058] The adhesive structure-forming curable composition contains a glycidylamine epoxy compound, an oxetane compound, and a cationic polymerization initiator. The proportion of the glycidylamine epoxy compound in the curable composition is 10% by mass or more. The adhesive structure-forming curable composition further contains other components as needed.

[0059] The viscosity of the curable composition for forming the above-mentioned adhesive structure is not particularly limited as long as it is a viscosity that can be ejected by inkjet printing. The viscosity can be appropriately selected according to the purpose, but it is preferably 200mPa·s or less at 25°C, and more preferably 50mPa·s or less. If the viscosity of the curable composition for forming the adhesive structure at 25°C is 200mPa·s or less, even if the curable composition for forming the adhesive structure is not heated to a high temperature, the adhesive structure can be thinly and evenly coated by inkjet printing. In addition, if the viscosity of the curable composition for forming the adhesive structure at 25°C is 200mPa·s or less, it is easy to adjust the coating amount, and the adhesive structure can be thinned, so the filling property is improved, and the generation of bubbles and voids can be reduced. Therefore, the filling performance of the wiring part such as the lead bonding and flip chip of the semiconductor (chip) is particularly improved, and patterned coating can be performed in a desired pattern, and the peeling of the adhesive structure can be suppressed.

[0060] The lower limit of the viscosity of the adhesive structure-forming curable composition is not particularly limited as long as it is a viscosity that allows the composition to be ejected by an inkjet printing method.

[0061] The viscosity of the adhesive structure-forming curable composition can be adjusted by the structures and ratios of the glycidylamine-type epoxy compound and the oxetane compound, other added components, and the like.

[0062] The viscosity of the curable composition for forming an adhesive structure at 25°C can be measured by conventional methods, for example, by the method described in JIS (Japanese Industrial Standard) Z8803. As another example, a cone-plate type rotational viscometer (e.g., VISCOMETER TVE-22L, manufactured by Toki Sangyo Co., Ltd.) can be used, using a conical rotor (1°34'×R24), with a rotation speed of 10 rpm and a constant temperature circulating water temperature of 25°C for measurement. The temperature of the circulating water is adjusted using a circulating thermostatic bath (e.g., VISCOM ATE VM-150III, manufactured by Toki Sangyo Co., Ltd.).

[0063] 《Glycidylamine type epoxy compounds》

[0064] The glycidylamine type epoxy compound (monomer) is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include, but are not limited to, compounds represented by the following general formula (1) and compounds represented by the following general formula (2). These compounds can be used alone or in combination.

[0065] [Chemical formula 1]

[0066]

[0067] In the above general formula (1), R1 It represents a monovalent aliphatic, aromatic, or alicyclic hydrocarbon group, or a group in which two or more groups selected from aliphatic, aromatic, or alicyclic hydrocarbon groups are bonded, and further represents a group in which a glycidyl ether group is bonded to these hydrocarbon groups or the group in which two or more hydrocarbon groups are bonded.

[0068] [Chemical formula 2]

[0069]

[0070] In the above general formula (2), R 2 It represents a monovalent aliphatic, aromatic, or alicyclic hydrocarbon group, or a group in which two or more selected from aliphatic, aromatic, or alicyclic hydrocarbon groups are bonded.

[0071] Specific examples of the glycidylamine type epoxy compound include, but are not limited to, compounds represented by any one of the following structural formulas 1 to 9. These compounds may be used alone or in combination.

[0072] [Chemical formula 3]

[0073]

[0074] Among these compounds, from the perspective of good adhesion and heat resistance of the adhesive structure as a cured product of the curable composition for forming the above-mentioned adhesive structure, it is preferred to contain at least any one trifunctional or higher glycidylamine-type epoxy compound selected from the group consisting of the compound represented by the above-mentioned structural formula 5, the compound represented by the above-mentioned structural formula 6, the compound represented by the above-mentioned structural formula 7, the compound represented by the above-mentioned structural formula 8 and the compound represented by the above-mentioned structural formula 9.

[0075] The glycidylamine type epoxy compound can be appropriately synthesized, or a commercially available product can be used.

[0076] Commercially available products of glycidylamine-type epoxy compounds include, for example, SUMI-EPOXY ELM-434, ELM-434VL, ELM-100 (manufactured by Sumitomo Chemical Co., Ltd.), ADEKA RESIN EP-3950S, P-3950L, EP-3980S (manufactured by ADEKA Corporation), YH-523, YH-513, YH-404 (manufactured by Nippon Steel Chemical Co., Ltd.), TETRAD-X (manufactured by Mitsubishi Gas Chemical Co., Ltd.), but are not limited to these.

[0077] Relative to the gross mass of the curable composition for forming an adhesive structure, the ratio of the glycidylamine type epoxy compound in the curable composition for forming an adhesive structure is 10% by mass or more, preferably 10% by mass or more and 40% by mass or less, more preferably 15% by mass or more and 30% by mass or less. When the ratio of the glycidylamine type epoxy compound is less than 10% by mass, the heat resistance and adhesion of the adhesive structure obtained by the curable composition for forming an adhesive structure are reduced. On the other hand, when the ratio of the glycidylamine type epoxy compound is 10% by mass or more, the heat resistance and adhesion of the adhesive structure of the cured product of the curable composition for forming an adhesive structure are good. In addition, the thermal stability of the curable composition for forming an adhesive structure of a mixed cationic polymerization initiator is improved. By making the ratio of the glycidylamine type epoxy compound 40% or less by mass, the viscosity of the curable composition for forming an adhesive structure can be easily set to a viscosity that can be ejected by an inkjet printing method.

[0078] 《Oxetane compounds》

[0079] Oxetane compound can adjust the viscosity of the curable composition for forming the above-mentioned adhesive structure, and can particularly reduce the viscosity caused by glycidylamine type epoxy compound.Thermosetting reaction is fast, therefore, by heating, each component is difficult to evaporate, and it is difficult to produce bubbles (voids) in the adhesive structure of the cured product of the curable composition for forming the adhesive structure.In addition, flexibility can be given to the adhesive structure of the cured product of the curable composition for forming the adhesive structure.Specifically, at least any one of the polymerization between glycidylamine type epoxy compound and oxetane compound and between oxetane compound, the longer the chain, the more high flexibility can be given.If conventional acrylonitrile copolymer (rubber), (meth) acrylic acid monomer, etc. are used instead of oxetane compound, the viscosity of the composition increases, and there is a composition that is difficult to obtain a viscosity suitable for being discharged by inkjet printing method, and the material that can be used for thermosetting reaction is limited. Therefore, the adhesive structure-forming curable composition of the present embodiment has a viscosity that allows it to be ejected by inkjet printing, and the adhesive structure-forming curable composition includes a glycidylamine-type epoxy compound and an oxetane compound, so that low molecular weight monomers are crosslinked by a thermal curing reaction.

[0080] As an oxetane compound (monomer), as long as it is a compound that can set the viscosity of the curable composition for forming an adhesive structure to a viscosity that can be ejected by an inkjet printing method, there is no particular limitation. The oxetane compound can be appropriately selected according to the purpose, and examples thereof include but are not limited to compounds represented by the following general formula (3) and compounds represented by the following general formula (4). These oxetane compounds can be used alone or in combination.

[0081] [Chemical formula 4]

[0082]

[0083] In the above general formula (3), R 3 It represents a monovalent organic group.

[0084] Specific examples of the compound represented by the general formula (3) include compounds represented by any one of the following structural formulas 10 to 15, but are not limited thereto.

[0085] [Chemical formula 5]

[0086]

[0087] [Chemical formula 6]

[0088]

[0089] In the above general formula (4), R 4 represents a divalent hydrocarbon group, or contains R 5 -OR 6 or R 5 -OR 6 -OR 7 A divalent organic group having an ether group. 5 , R 6 and R 7 Each independently represents a hydrocarbon group. 5 , R 6 and R 7 Can be the same or different.

[0090] Specific examples of the compound represented by the general formula (4) include compounds represented by any one of the following structural formulas 16 to 18, but are not limited thereto.

[0091] [Chemical formula 7]

[0092]

[0093] (In structural formula 17, n represents an integer of 1 or 2)

[0094] Among them, from the perspective of being able to obtain a viscosity that can be ejected by inkjet printing and having good adhesion and softness as an adhesive structure of a cured product of a curable composition for forming an adhesive structure, it is preferred to contain at least any one compound selected from the group consisting of the compound represented by the above structural formula 10, the compound represented by the above structural formula 12, the compound represented by the above structural formula 16 and the compound represented by the above structural formula 17.

[0095] From the viewpoint of flexibility of the adhesive structure, the oxetane compound alone preferably has a glass transition temperature (Tg) of a cured product of 100° C. or less.

[0096] The glass transition temperature (Tg) of the cured product of the oxetane compound monomer can be measured as follows. 1% by mass of SAN-AID SI-150 (manufactured by Sanshin Chemical Industry Co., Ltd.) as a thermal polymerization initiator is added to the oxetane compound, and the resulting solution is injected between two glass plates. Next, the glass plates are heated at 100°C for 2 hours, then at 200°C for 1 hour, and then thermally cured at 260°C for 5 minutes. Then, the cured product is peeled off from the two glass plates, a sample for measurement is prepared, and the glass transition temperature is measured under the following measurement conditions using a rheometer (manufactured by TA Instruments, ARES-G2).

[0097] [Measurement conditions]

[0098] -Measurement method: Torsional vibration

[0099] -Test sample set: Tensile force: 10gf (gap variable: initial value about 10mm)

[0100] -Strain condition: minimum torque 0.3g·cm (variable strain: initial value 0.05%, maximum value 1%)

[0101] - Temperature: 25℃ to 300℃, 20℃ / min

[0102] - Sample shape: about 20mm×5mm (thickness: 100μm)

[0103] From the viewpoint of imparting photocurability and heat curability, the oxetane compound preferably contains an oxetane acrylate having an oxetane acrylate group. When the oxetane compound contains an oxetane acrylate, good adhesive strength can be obtained when photocuring and heat curing are used in combination. The oxetane acrylate preferably contains the compound shown in the above structural formula 15.

[0104] The oxetane compound may be appropriately synthesized, or a commercially available product may be used.

[0105] Examples of commercially available oxetane compounds include ARON OXETANE OXT-101, ARON OXETANE OXT-212, ARON OXETANE OXT-121, ARON OXETANE

[0106] OXT-221 (all manufactured by Toagosei Co., Ltd.), ETERNACOLL (registered trademark) HBOX, OXBP, OXIPA (all manufactured by Ube Industries, Ltd.), OXE-10 ((3-ethyloxetane-3-yl) methyl acrylate), OXE-30 ((3-ethyloxetane-3-yl) methyl methacrylate), MEDOL-10 ((3-ethyloxetane-3-yl) methyl acrylate) (all manufactured by Osaka Organic Chemical Industry Co., Ltd.), etc., but are not limited to these.

[0107] The ratio of the oxetane compound in the curable composition for adhesive structure formation is not particularly limited as long as it has a ratio of viscosity that can eject the adhesive structure formation curable composition by inkjet printing. The ratio of the oxetane compound can be appropriately selected according to the type of glycidylamine type epoxy compound, etc. However, the ratio of the oxetane compound is preferably 10% by mass or more and 60% by mass or less, and more preferably 20% by mass or more and 40% by mass or less. By making the ratio of the oxetane compound more than 10% by mass, the flexibility of the adhesive structure obtained by the adhesive structure formation curable composition is good, and the viscosity of the adhesive structure formation curable composition can be set to a viscosity suitable for ejecting by inkjet printing. By making the ratio of the oxetane compound less than 60% by mass, the heat resistance and adhesion of the adhesive structure obtained by the adhesive structure formation curable composition become good.

[0108] When the adhesive structure-forming curable composition contains the above-mentioned other components, the ratio of the above-mentioned oxetane compound is a ratio relative to the total mass of the adhesive structure-forming curable composition.

[0109] 《Cationic polymerization initiator》

[0110] The cationic polymerization initiator includes a thermal cationic polymerization initiator and a photocationic polymerization initiator.

[0111] In the case of obtaining an adhesive structure formed by an epoxy resin, the adhesive structure forming curable composition contains a thermal cationic polymerization initiator, and the adhesive structure forming curable composition formed between the substrates as two bonding objects can be bonded by thermal curing. In addition, when the substrate material has light transmittance, the cationic polymerization initiator can contain a photocationic polymerization initiator, and therefore, the curable composition for the adhesive structure formation can be irradiated with light to make it photocured. In addition, the cationic polymerization initiator can contain a thermal cationic polymerization initiator and a photocationic polymerization initiator, so that a bonding method that is cured by using both heat and light can be adopted.

[0112] -Thermal Cationic Polymerization Initiator-

[0113] The thermal cationic polymerization initiator is not particularly limited and can be appropriately selected according to the purpose. As the thermal cationic polymerization initiator, it is not particularly limited, for example, photoacid generators such as onium salts having sulfonium ions or iodonium ions as the cationic part can be cited. Among these thermal cationic polymerization initiators, it is preferred that the cationic part of the thermal cationic polymerization initiator is a sulfonium ion. In addition, it is preferred that the thermal cationic polymerization initiator is a compound having an anionic part with low corrosivity to metal parts.

[0114] Specific examples of the anion part (generated acid) include compounds such as B(C6F5)4 and PF3(C2F5)3, but are not limited to these.

[0115] The thermal cationic polymerization initiator may be synthesized as appropriate, or a commercially available product may be used.

[0116] There are no particular limitations on commercially available thermal cationic polymerization initiators, and examples thereof include SAN-AID SI-60, SAN-AID SI-80, SAN-AID SI-100, SAN-AID SI-110, SAN-AID SI-150 (all manufactured by Sanshin Chemical Industries, Ltd.), TA-100, TA-100FG, IK-1, IK-1FG (manufactured by San-Apro), OMNICAT 250 (former IRGACURE 250), OMNICAT 270 (former IRGACURE 270) (all manufactured by IGM Resins BV), and the like.

[0117] The ratio of the thermal cationic polymerization initiator in the curable composition for adhesive structure formation is not particularly limited and can be appropriately selected according to the purpose. However, relative to the gross mass of the curable composition for adhesive structure formation, the ratio of the thermal cationic polymerization initiator is preferably 0.1 mass % or more and 10 mass % or less, more preferably 1 mass % or more and 10 mass % or less. If the ratio of the thermal cationic polymerization initiator is 0.1 mass % or more and 10 mass % or less, the curing reaction can be suitably completed, and the unreacted components are unlikely to remain as reactive impurities.

[0118] --Photocationic polymerization initiator--

[0119] The photocationic polymerization initiator is not particularly limited and can be appropriately selected according to the purpose. As the photocationic polymerization initiator, it is not particularly limited, for example, a photoacid generator such as an onium salt having a sulfonium ion or an iodonium ion as a cationic part can be cited. These photocationic polymerization initiators can be used alone or in combination. Among these photocationic polymerization initiators, compounds having an anion part with low corrosiveness to metal parts are preferred.

[0120] Specific examples of the photocationic polymerization initiator include compounds containing B(C6F5)4 or PF3(C2F5)3 as an anion portion (generating acid), but are not limited thereto.

[0121] As the photocationic polymerization initiator, one may be appropriately synthesized or a commercially available one may be used.

[0122] Commercially available products of photocationic polymerization initiators include, but are not limited to, CPI (registered trademark)-110P, CPI (registered trademark)-110A, CPI (registered trademark)-210S, CPI (registered trademark)-110B, CPI (registered trademark)-310B, CPI (registered trademark)-410B, CPI (registered trademark)-310FG, and IK-1FG (all manufactured by San-Apro Co., Ltd.).

[0123] The proportion of the cationic polymerization initiator can be confirmed by the proportion of the reaction residues (eg, sulfides) contained in the adhesive structure. The material composition in the adhesive structure can be analyzed by thermal decomposition gas chromatography-mass spectrometry (GC / MS) and real-time mass spectrometry (DART-MS).

[0124] 《Other ingredients》

[0125] The adhesive structure-forming curable composition may contain other components besides the glycidylamine-type epoxy compound and the oxetane compound within a range not impairing the effects of the present invention.

[0126] Glycidylamine epoxy compounds and oxetane compounds have low molecular weights and thus low viscosities at room temperature (about 25° C.), thereby improving the range of options and mixing ratios of other materials to be added. Thus, it is easy to optimize the curable composition for forming an adhesive structure according to the application.

[0127] The other components are not particularly limited and can be appropriately selected according to the purpose. Examples thereof include, but are not limited to, monomers other than glycidylamine-type epoxy compounds and oxetane compounds, organosilicon compounds, inorganic particles, resins and / or resin particles, adhesion improvers, and polymerization initiators other than the above-mentioned cationic polymerization initiators. Each of these components can be used alone or in combination with other components.

[0128] -Monomers other than glycidylamine type epoxy compounds and oxetane compounds-

[0129] By making the adhesive structure-forming curable composition contain monomers other than the glycidylamine epoxy compound and the oxetane compound, the compatibility between the glycidylamine epoxy compound and the oxetane compound can be improved. In addition, since the viscosity of the adhesive structure-forming curable composition can be easily adjusted to a more appropriate viscosity, it is easy to adjust the film elasticity of the adhesive structure as a cured product of the adhesive structure-forming curable composition, thereby improving the adhesion. In addition, a photocuring function can also be imparted.

[0130] Monomers other than glycidylamine epoxy compounds and oxetane compounds are not particularly limited and can be appropriately selected according to the purpose. Examples include, but are not limited to, alicyclic epoxy compounds, glycidyl ether epoxy compounds, (meth) acrylate monomers, and urethane monomers. These can be used alone or in combination. Among them, from the viewpoint of adjusting the viscosity of the curable composition for forming an adhesive structure, and the bonding strength of the adhesive structure of the cured product of the curable composition for forming an adhesive structure, it is preferred to contain an alicyclic epoxy compound or a glycidyl ether epoxy compound.

[0131] The ratio of monomers other than glycidylamine epoxy and oxetane compounds in the curable composition is not particularly limited as long as it does not damage the effect of the present invention, and can be appropriately selected according to the purpose. However, relative to the gross mass of the curable composition for adhesive structure formation, the ratio is preferably 1% by mass or more and 60% by mass or less, more preferably 5% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 30% by mass or less. If the ratio of monomers other than glycidylamine epoxy and oxetane compounds is 1% by mass or more and 60% by mass or less, the compatibility of glycidylamine epoxy and oxetane compounds is excellent, and viscosity can be reduced. If the ratio of monomers other than glycidylamine epoxy and oxetane compounds is 5% by mass or more and 30% by mass or less, the characteristics of the cured product of the glycidylamine epoxy and oxetane compounds as the main components are not damaged, and the adhesive structure as a cured product can be obtained.

[0132] --Alicyclic Epoxides--

[0133] The curing reaction of the alicyclic epoxy compound is fast, so the manufacturing efficiency of the adhesive structure can be improved. In addition, the glass transition temperature (Tg) of the cured product of the alicyclic epoxy compound is high, so heat resistance can be imparted to the adhesive structure as a cured product of the curable composition for forming an adhesive structure.

[0134] The alicyclic epoxy compound (monomer) is not particularly limited as long as it has a viscosity that allows the curable composition for forming an adhesive structure to be ejected by inkjet printing. The alicyclic epoxy compound can be appropriately selected according to the purpose, and examples thereof include, but are not limited to, compounds represented by the following general formula (5) and compounds represented by the following general formula (6). These compounds can be used alone or in combination.

[0135] [Chemical formula 8]

[0136]

[0137] In the above general formula (5), X and Y each independently represent a hydrocarbon containing one or more saturated or unsaturated carbocyclic rings and not having aromaticity, and n represents an integer of 0 to 3. 0, 1, or 2 monovalent organic groups are bonded to the carbon atoms of the carbocyclic rings of X and Y. X and Y may be the same or different.

[0138] Among them, the compound represented by the above general formula (5) is preferably a compound represented by the following general formula (5a).

[0139] [Chemical formula 9]

[0140]

[0141] In the above general formula (5a), X1 and Y1 each independently represent a 5-membered or 6-membered saturated carbocyclic ring. The carbon atoms of the carbocyclic rings of X1 and Y1 are bonded to 0, 1, or 2 monovalent organic groups. X1 and Y1 may be the same or different.

[0142] Specific examples of the compound represented by the general formula (5) include compounds represented by any one of the following structural formulas 19 to 26, but are not limited thereto.

[0143] [Chemical formula 10]

[0144]

[0145] [Chemical formula 11]

[0146]

[0147] In the above general formula (6), X and Y each independently represent a hydrocarbon containing one or more saturated or unsaturated carbon rings and not having aromaticity, Z represents an alicyclic hydrocarbon or a monofunctional alicyclic epoxy, and m represents an integer of 0 or 1. 0, 1, or 2 monovalent organic groups are bonded to the carbon atoms of the carbon rings of X and Y. X and Y may be the same or different.

[0148] Among them, the compound represented by the above general formula (6) is preferably a compound represented by the following general formula (6a).

[0149] [Chemical formula 12]

[0150]

[0151] In the above general formula (6a), X1 and Y1 each independently represent a 5-membered or 6-membered saturated carbocyclic ring. The carbon atoms of the carbocyclic rings of X1 and Y1 are bonded to 0, 1, or 2 monovalent organic groups. X1 and Y1 may be the same or different.

[0152] Specific examples of the compound represented by the general formula (6) and the compound represented by the general formula (6a) include compounds represented by any one of the following structural formulas 27 to 32, but are not limited thereto.

[0153] [Chemical formula 13]

[0154]

[0155] In addition, examples of the alicyclic epoxy compound include, but are not limited to, a compound represented by the following structural formula 33, a compound represented by the following structural formula 34, and a compound represented by the following structural formula 35.

[0156] [Chemical formula 14]

[0157]

[0158] (In the above structural formula 34, n represents an integer of 1 or 2)

[0159] Among them, the alicyclic epoxy compound preferably includes at least one compound selected from the group consisting of a compound represented by structural formula 20, a compound represented by structural formula 22, a compound represented by structural formula 27, a compound represented by structural formula 28, and a compound represented by structural formula 29, so that the viscosity of the curable composition can be obtained so that it can be discharged by an inkjet printing method, so that the adhesive structure has good adhesion and heat resistance.

[0160] The alicyclic epoxy compound may be appropriately synthesized, or a commercially available product may be used.

[0161] Commercially available products of alicyclic epoxy compounds include, but are not limited to, EPOCHALIC THI-DE, EPOCHALIC DE-102, EPOCHALIC DE-103, VNBB-ME (all manufactured by ENEOS), DCPD-DE (manufactured by Nippon Material Technology Co., Ltd.), CELLOXIDE (CEL) 8010P, CEL2010P, CEL2081, CEL2000 (all manufactured by Daicel Corporation), and the like.

[0162] --Glycidyl ether type epoxy compounds--

[0163] The glycidyl ether type epoxy compound (monomer) is not particularly limited and can be appropriately selected according to the purpose. As the glycidyl ether type epoxy compound, it is not particularly limited, and allyl diglycidyl ether, bisphenol type diglycidyl ether, etc. can be mentioned. These glycidyl ether type epoxy compounds can be used alone or in combination.

[0164] Specific examples of the glycidyl ether type epoxy compound include, but are not limited to, compounds represented by any of the following structural formulas 36 to 43. These compounds may be used alone or in combination.

[0165] [Chemical formula 15]

[0166]

[0167] (In the above structural formula 36, ​​n represents 12, and in the structural formula 38, n represents 9)

[0168] The glycidyl ether type epoxy compound can be appropriately synthesized, or a commercially available product can be used.

[0169] Examples of commercially available glycidyl ether epoxy compounds include RIKARESIN DME-100 (manufactured by Shin Nippon Rika Co., Ltd.), EPOLIGHT M-1230, EPOLIGHT 40E, EPOLIGHT 100E, EPOLIGHT 200E, EPOLIGHT 400E, EPOLIGHT 70P, EPOLIGHT 200P, EPOLIGHT 400P, EPOLIGHT 1500NP, EPOLIGHT 1600, EPOLIGHT 80MF, and EPOLIGHT 100MF (all manufactured by Kyoeisha Chemical Co., Ltd.), SHOFREE (registered trademark) PETG, SHOFREE (registered trademark) BATG (all manufactured by Showa Denko K.K.), DENACOL EX-614B, DENACOL EX-313, DENACOL EX-512, DENACOL EX-321, DENACOL EX-321L, and DENACOL EX-612, DENACOL EX-614, DENACOL EX-622, DENACOL EX-314, DENACOL EX-421, DENACOL EX-521, DENACOL EX-411, DENACOL EX-171, DENACOL EX-146, DENACOL EX-121, DENACOL EX-141, DENACOL EX-145, DENACOL EX-147, DENACOL EX-192, EPOLIGHT EX-731, DENACOL EX-991L (all manufactured by Nagase Chemicals Co., Ltd.), YL9028 (manufactured by Mitsubishi Chemical Corporation), EGPOSEY (registered trademark) OCR-EP, EGPOSEY (registered trademark) NPG (D), DY-BP, EGPOSEY (registered trademark) HD ​​(D) (all manufactured by Yokkaichi Chemical Co., Ltd.), etc., but are not limited to these.

[0170] --(Meth)acrylate monomers--

[0171] The (meth)acrylate monomer is not particularly limited and can be appropriately selected from conventional photopolymerizable or thermally polymerizable (meth)acrylate monomers according to the purpose. These monomers can be used alone or in combination. In the present invention, "(meth)acrylate monomer" is a general term for "acrylate monomer" and "methacrylate monomer".

[0172] The (meth)acrylate monomer may be appropriately synthesized, or a commercially available product may be used.

[0173] Commercially available products of (meth)acrylate monomers include, but are not limited to, AOMA (registered trademark) (manufactured by Nippon Shokubai Co., Ltd.), HEA (hydroxyethyl acrylate), HPA (hydroxypropyl acrylate), 4-HBA (4-hydroxybutyl acrylate), AIB (isobutyl acrylate), TBA (tert-butyl acrylate), NOAA (n-octyl acrylate), INAA (isononyl acrylate), VISCOAT #197 (nonyl acrylate), IDAA (nonyl acrylate), LA (lauryl acrylate), STA (stearyl acrylate), ISTA (isobutyl acrylate), and 1,1-dimethoxy- ... stearyl acrylate), IBXA (isobornyl acrylate), VISCOAT#155 (cyclohexyl acrylate), VISCOAT#196 (3,3,5-trimethylcyclohexyl acrylate), VISCOAT#160 (benzyl acrylate), VISCOAT#192 (phenoxyethyl acrylate), VISCOAT#150 (tetrahydrofuranyl acrylate), VISCOAT#190 (carbitol acrylate), 2-MTA (methoxyethyl acrylate), VISCOAT#MTG (methoxytriethylene glycol acrylate), Bismer MPE400A (methoxy polyethylene glycol acrylate), Bismer MPE550A (methoxy polyethylene glycol acrylate), VISCOAT #200 (cyclotrimethylolpropane formal acrylate) (all manufactured by Osaka Organic Chemical Industry Co., Ltd.), A-LEN-10 (ethoxylated o-phenylphenol acrylate), AM-90G (ethoxylated o-phenylphenol acrylate), AM-130G (ethoxylated o-phenylphenol acrylate), AMP-20GY (ethoxylated o-phenylphenol acrylate), A-SA (2-acryloyloxyethyl succinic acid), 701A (propyl acrylate 2-hydroxy-3-methacrylate), A-200 (polyethylene glycol)

[0174] A-200 (polyethylene glycol #400 diacrylate), A-400 (polyethylene glycol #400 diacrylate), A-600 (polyethylene glycol #600 diacrylate), A-100 (polyethylene glycol #100 diacrylate), ABE-300 (ethoxylated bisphenol-A diacrylate), A-BPE-10 (ethoxylated bisphenol-A diacrylate), A-BPE-20 (ethoxylated bisphenol-A diacrylate), A-BPE-4 (ethoxylated bisphenol-A diacrylate), Acrylate), A-DCP (tricyclodecane dimethanol diacrylate), A-DOD-N (1,10-decanediol diacrylate), A-HD-N (1,6-hexanediol diacrylate), A-NOD-N (1,6-hexanediol diacrylate), APG-200 (tripropylene glycol diacrylate), APG-400 (polypropylene glycol #400 diacrylate), APG-700 (polypropylene glycol #700 diacrylate), A-PTMG -65 (polytetramethylene glycol #650 diacrylate), A-9300 (polytetramethylene glycol #650 diacrylate), A-GLY-9E (ethoxylated glyceryl triacrylate), A-GLY-20E (ethoxylated glyceryl triacrylate), A-TMM-3 (pentaerythritol tri- and tetraacrylates), A-TMM-3L (pentaerythritol tri- and tetraacrylates), A-TMPT (trimethylolpropane triacrylate), AD-TMP (ditrimethylolpropane tetraacrylate), ATM-35E (ethoxylated pentaerythritol tetraacrylate), A-TMMT (pentaerythritol tetraacrylate), A-9550 (dipentaerythritol polyacrylate), A-DPH (dipentaerythritol polyacrylate) (all manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), SR440 (isooctyl acrylate), SR849D (tridecyl acrylate), SR395 (isodecyl acrylate) (all manufactured by Tomoe Engineering Co., Ltd.).

[0175] --Urethane Monomer--

[0176] The urethane monomer is not particularly limited and can be appropriately selected from common urethane monomers according to the purpose. These may be used alone or in combination with other monomers.

[0177] The urethane monomer may be appropriately synthesized, or a commercially available product may be used.

[0178] Commercially available products of the urethane monomer include, but are not limited to, UF-3003, UF-3003M, UF-3007, UF-3007M, and UF-3123M (all manufactured by Kyoeisha Chemical Co., Ltd.).

[0179] -Organic silicon compounds-

[0180] The organosilicon compound is not particularly limited and can be appropriately selected from common organosilicon compounds according to the purpose, for example, an organosilicon compound having a reactive group at one or both ends of polydimethylsiloxane, etc. These can be used alone or in combination with other compounds.

[0181] The organosilicon compound may be synthesized as appropriate, or a commercially available product may be used.

[0182] Commercially available products of the organic silicon compound include, but are not limited to, Silaplane (registered trademark) FM-3311, Silaplane (registered trademark) FM-3321, Silaplane (registered trademark) FM-3325 (all manufactured by JNC Corporation), STP-103-UV, STP-104-UV (all manufactured by Shin-Etsu Silicone Co., Ltd.), and the like.

[0183] As long as the effect of the present invention is not damaged, there is no particular restriction on the ratio of the organosilicon compound in the curable composition, and the ratio can be appropriately selected according to the purpose. However, relative to the gross mass of the curable composition for forming the adhesive structure, the ratio of the organosilicon compound is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 50% by mass or less, and further preferably 5% by mass or more and 30% by mass or less. The ratio of the organosilicon compound is preferably 1% by mass or more and 50% by mass or less, because in this case, the compatibility of the glycidylamine type epoxy compound and the oxetane compound is excellent, and the viscosity can be reduced. The ratio of the organosilicon compound is more preferably 5% by mass or more and 30% by mass or less, because in this case, the adhesive structure as a cured product can be obtained without damaging the characteristics of the cured product of the glycidylamine type epoxy compound and the oxetane compound as the main component.

[0184] --Inorganic particles--

[0185] By making the adhesive structure-forming curable composition contain inorganic particles, the linear thermal expansion coefficient of the adhesive structure is further reduced, and the strength of the adhesive structure as a cured product of the adhesive structure-forming curable composition can be further improved.

[0186] There is no particular limitation on the inorganic particles, and they can be appropriately selected from known inorganic particles. Examples of inorganic particles include, but are not limited to, ceramic materials, metal materials, and magnetic particles. These inorganic particles can be used alone or in combination.

[0187] Examples of ceramic materials include, but are not limited to, silicon dioxide (SiO2), aluminum oxide (Al2O3), aluminum nitride (AlN), and boron nitride (BN). Compared with resin materials, the ceramic material has a small linear thermal expansion coefficient and a high glass transition temperature, so it is possible to obtain an effect of reducing the linear thermal expansion coefficient of the adhesive structure and improving the film strength under high temperature conditions. Therefore, when the adhesive structure is heated at high temperatures, the function of inhibiting thermal expansion can be imparted.

[0188] Examples of metallic materials include, but are not limited to, metals such as Au, Ag, Pd, Cu, Ni, Pt, Fe, and Co; and solders such as Sn / Pb, Sn / Ag / Cu. The metallic material particles can impart electrical conductivity to the adhesive structure.

[0189] Examples of the magnetic particles include, but are not limited to, iron (Fe), nickel (Ni), and cobalt (Co). The magnetic particles may impart a function of shielding electromagnetic waves.

[0190] The inorganic particles may be appropriately synthesized, or commercially available particles may be used.

[0191] Examples of commercially available inorganic particles include, but are not limited to, AEROSIL (registered trademark) OX50, AEROSIL (registered trademark) 50, AEROSIL (registered trademark) 90G, AEROSIL (registered trademark) 130, AEROSIL (registered trademark) 150, AEROSIL (registered trademark) 200, AEROSIL (registered trademark) 300, AEROSIL (registered trademark) 380, AEROSIL (registered trademark) RM50, AERO SIL (registered trademark) R711, AEROSIL (registered trademark) R7200, AEROXIDE (registered trademark) P25, AEROXIDE (registered trademark) P90 AluC (all manufactured by AEROSIL Co., Ltd. of Japan), Seahostar (registered trademark) KE-S10, Seahostar (registered trademark) S30, and Seahostar (registered trademark) S50 (all manufactured by Nippon Shokubai Co., Ltd.).

[0192] The primary average particle size (D50) of the inorganic particles is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.1 μm or more and 5 μm or less, more preferably 0.1 μm or more and 1 μm or less. By making the primary average particle size (D50) of the inorganic particles 0.1 μm or more, the viscosity increase of the curable composition for forming an adhesive structure can be suppressed. When the primary average particle size (D50) of the inorganic particles is 5 μm or less, when the curable composition for forming an adhesive structure is ejected by an inkjet printing method, the fine nozzle hole is not easily clogged.

[0193] The primary average particle size (D50) of the inorganic particles can be measured by dynamic image analysis, dynamic light scattering (DLS) or the like.

[0194] The ratio of the inorganic particles in the curable composition for forming the above-mentioned adhesive structure is not particularly limited, and can be appropriately selected according to the purpose. However, relative to the gross mass of the curable composition for forming the adhesive structure, the ratio of the inorganic particles is preferably more than 5 mass % and less than 70 mass %, more preferably more than 5 mass % and less than 50 mass %. When the ratio of the inorganic particles is more than 5 mass %, it is easy to obtain the effect of linear thermal expansion and film strength. When the ratio of the inorganic particles is less than 70 mass %, the adhesive structure is not easy to become brittle, and the viscosity of the curable composition for forming the adhesive structure can be suppressed to rise, therefore, it is possible to be suitable for inkjet printing.

[0195] --resin and / or resin particles--

[0196] By making the adhesive structure-forming curable composition contain resin and / or resin particles, the flexibility, heat resistance and adhesion of the adhesive structure as a cured product of the adhesive structure-forming curable composition can be further improved, and thermal stress can be further alleviated. In addition, since the viscosity of the adhesive structure-forming curable composition can be easily adjusted to a more appropriate viscosity, it is easy to adjust the elasticity of the adhesive structure as a cured product of the adhesive structure-forming curable composition.

[0197] The resin and / or resin particles are not particularly limited and can be appropriately selected according to the purpose as long as the effect of the present embodiment is not impaired. However, the resin and / or resin particles preferably have a low glass transition temperature (Tg) to reduce thermal stress, and more preferably have a glass transition temperature (Tg) of about 30°C or less, which is approximately the same as room temperature.

[0198] The glass transition temperature (Tg) of the resin and / or the resin particles can be measured by a thermal analysis method such as TG-DTA and DSC.

[0199] As the resin and / or resin particles, it is preferred to use a material containing a straight-chain polymer having at least one characteristic of low elasticity and softness. As resin and / or resin particles, there is no particular limitation, and examples thereof include styrene-butadiene resin, acrylonitrile-butadiene resin, (meth) acrylic resin, epoxy resins other than resins formed by multifunctional alicyclic epoxy compounds, polyurethane resins, phenolic resins, polyimide resins, ester resins, vinyl resins, silicone resins, styrene resins, cellulose resins, amide resins, (meth) acrylic resins, melamine resins, fluorine resins, and various mixtures of these resins. These resins can be used alone or in combination. In addition, polymer particles having a core-shell multilayer structure in which a rubber-like polymer is arranged inside an acrylic copolymer can also be used. Among these resins and / or resin particles, from the aspect of good heat resistance, styrene-butadiene resin, (meth) acrylic resin, epoxy resins other than alicyclic epoxy compounds, silicone resins, and polyimide resins are preferred.

[0200] Here, the resin and / or resin particles being "low elastic" means a material having an elastic modulus of 200 MPa or less.

[0201] The elastic modulus of the resin and / or the resin particles can be obtained by measuring the indentation elastic modulus using a microhardness tester (for example, FISCHERSCOPE (registered trademark) HM2000 manufactured by Fischer Instruments Inc.), for example.

[0202] The “flexibility” of the resin and / or resin particles refers to a material having an elastic deformation rate of 70% or more.

[0203] The elastic deformation rate of the resin and / or the resin particles can be confirmed by measuring the indentation elastic modulus using a microhardness tester (for example, FISCHERSCOPE (registered trademark) HM2000, manufactured by Fischer Instruments).

[0204] The resin and / or resin particles may be appropriately synthesized, or a commercially available product may be used.

[0205] Examples of commercially available resins include, but are not limited to, ARUFON (registered trademark) US-1000, ARUFON (registered trademark) UH-2000, ARUFON (registered trademark) UC-3000, ARUFON (registered trademark) UG-4000, ARUFON (registered trademark) UF-5000, and ARUFON (registered trademark) US-600.

[0206] Commercially available products of the resin particles include, but are not limited to, Kane Ace (registered trademark) MX-150, Kane Ace (registered trademark) MX-553 (all manufactured by Kaneka Co., Ltd.), Finesphere (registered trademark) MG-155, Finesphere (registered trademark) MG-351, Finesphere (registered trademark) MG-451, Finesphere (registered trademark) MG-651, Finesphere (registered trademark) PZP-1003, Finesphere (registered trademark) BGK-001 (all manufactured by Nippon Paint Industrial Coatings Co., Ltd.), Metablen (registered trademark) C-223A, Metablen (registered trademark) C-215A-201A, Metablen (registered trademark) C-140A, Metablen (registered trademark) E-860A, Metablen (registered trademark) E-870A, Metablen (registered trademark) E-875A, Metablen (registered trademark) Metablen (registered trademark) W-300A, Metablen (registered trademark) W-450A, Metablen (registered trademark) W-600A, Metablen (registered trademark) W-377, Metablen (registered trademark) S-2002, Metablen (registered trademark) S-2006, Metablen (registered trademark) S-2501, Metablen (registered trademark) S-2030, Metablen (registered trademark) S-2100, Metablen (registered trademark) S-2200, Metablen (registered trademark) SRK200A, Metablen (registered trademark) SX-006, Metablen (registered trademark) SX-00 (all manufactured by Mitsubishi Chemical Corporation), Zefiac F351, Staphyloid AC-3355, AC-3816N, AC-3832SD, AC-4030 and AC-3388 (all manufactured by Aica Industries, Ltd.), etc.

[0207] The primary average particle size (D50) of the resin particles is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.1 μm or more and 5 μm or less, more preferably 0.1 μm or more and 1 μm or less. By making the primary average particle size (D50) of the resin particles 0.1 μm or more, the viscosity increase of the curable composition for forming an adhesive structure can be suppressed. When the primary average particle size (D50) of the resin particles is 5 μm or less, when the curable composition for forming an adhesive structure is ejected by an inkjet printing method, clogging of the nozzle pores is not likely to occur.

[0208] The primary average particle size (D50) of the resin particles can be measured by a dynamic image analysis method, a dynamic light scattering method (DLS), or the like.

[0209] As the content of the resin particles in the curable composition for forming the adhesive structure, there is no particular restriction, and it can be appropriately selected according to the purpose, relative to the gross mass of the curable composition for forming the adhesive structure, the ratio of resin particles is preferably 1 mass % or more and 50 mass % or less, more preferably 5 mass % or more and 50 mass % or less, and more preferably 3 mass % or more and 20 mass % or less. When the ratio of resin particles is more than 1 mass %, thermal stress can be more appropriately relaxed. By making the ratio of resin particles be less than 50 mass %, the viscosity rise of the curable composition for forming the adhesive structure can be suppressed, therefore, it can be suitable for inkjet printing, and it is not easy to produce bubbles, voids at high temperatures.

[0210] --Close contact improver--

[0211] By making the adhesive structure-forming curable composition contain an adhesion improver, the adhesiveness of the adhesive structure can be improved.

[0212] The adhesion improver is not particularly limited and can be appropriately selected according to the purpose. However, the adhesion improver contains organic matter and silicon, and the silane coupling agent having two or more different reactive groups in the molecule can improve the adhesion with the contact object (especially semiconductors and semiconductor substrates), so it is particularly preferred.

[0213] The adhesion improving agent may be synthesized as appropriate, or a commercially available product may be used.

[0214] Commercially available products of the adhesion improver include, but are not limited to, DOWSIL Z-6040 and DOWSIL Z-6062 (each manufactured by DOW), and KMB-403 (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0215] As the proportion of the adhesion improver in the curable composition for forming the adhesive structure, there is no particular restriction and can be appropriately selected according to the purpose. The proportion of the adhesion improver is preferably 0.1% by mass or more and 20% by mass or less, more preferably 0.1% by mass or more and 5% by mass or less relative to the gross mass of the curable composition for forming the adhesive structure. When the proportion of the adhesion improver is 0.1% by mass or more, an adhesive effect can be obtained. By making the proportion of the adhesion improver 20% by mass or less, the strength reduction of the cured product, i.e., the adhesive structure, obtained by the curable composition for forming the adhesive structure can be suppressed.

[0216] -Solvents-

[0217] The solvent is not particularly limited and can be appropriately selected according to the purpose, including, but not limited to, terpineol, 1-methoxy-2-propanol, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, 2-methoxyethyl acetate, 2-methoxybutyl acetate, 2-butanone, etc. These can be used alone or in combination with others.

[0218] The proportion of the solvent in the adhesive structure-forming curable composition is not particularly limited and may be appropriately selected depending on the intended purpose. However, if the viscosity of the adhesive structure-forming curable composition is appropriate, it is preferred that no solvent is contained.

[0219] In the case where the adhesive structure is formed with a curable composition containing a solvent, relative to the gross mass of the adhesive structure forming curable composition, the content of the solvent is preferably 1% by mass or more and 10% by mass or less, more preferably 1% by mass or more and 5% by mass or less. When the ratio of the solvent is 1% by mass or more, the solvent component of the adhesive structure forming curable composition can be easily managed, and the viscosity can be reduced, therefore, it can be suitable for inkjet printing. In addition, when the ratio of the solvent is 10% by mass or less, it is unlikely to generate bubbles or voids at high temperatures.

[0220] --Polymerization initiators other than cationic polymerization initiators--

[0221] As polymerization initiators other than cationic polymerization initiators, there are no particular limitations, and examples thereof include photoradical polymerization initiators, etc. The photoradical polymerization initiators are not particularly limited and can be appropriately selected according to the purpose. As photoradical polymerization initiators, alkyl phenyl ketone compounds, acyl phosphine oxide compounds, oxyphenyl acetate compounds, etc. can be cited. These compounds can be used alone or in combination.

[0222] The photoradical polymerization initiator may be synthesized as appropriate, or a commercially available product may be used.

[0223] Commercially available products of the photoradical polymerization initiator include, but are not limited to, Omnirad 184 (former Irgacure 184), Omnirad 651 (former Irgacure 651), Omnirad 1173 (former Irgacure 1173), Omnirad 2959 (former Irgacure 2959), Omnirad 369 (former Irgacure 369), Omnirad 907 (former Irgacure 907), Omnirad BMS, Omnirad DETX, Omnirad TPO H (former Irgacure TPO), Omnirad 819 (former Irgacure 819) (all manufactured by IGM Resins BV), Irgacure OXE01, Irgacure OXE02, Irgacure OXE03, Irgacure OXE04 (all manufactured by BASF JAPAN) and the like.

[0224] The ratio of the photopolymerization initiator in the curable composition for forming the above-mentioned adhesive structure is not particularly limited and can be appropriately selected according to the purpose. However, relative to the gross mass of the curable composition for forming the adhesive structure, the ratio of the photopolymerization initiator is preferably 0.1 mass % or more and 10 mass % or less, more preferably 0.2 mass % or more and 2 mass % or less. If the ratio of the photopolymerization initiator is 0.1 mass % or more and 10 mass % or less, the curing reaction can be properly completed, and the unreacted components are unlikely to remain as reactive impurities.

[0225] (Adhesive structures and cured products)

[0226] The adhesive structure of the present embodiment comprises a resin having a glycidylamine epoxy unit and an oxetane unit, and a component derived from a cationic polymerization initiator. The proportion of the glycidylamine epoxy unit in the resin is 10% by mass or more. If necessary, the adhesive structure comprises other components.

[0227] The cured product of the present embodiment is formed by curing the above-mentioned adhesive structure with a curable composition. Therefore, the cured product of the present embodiment has the same structure as the adhesive structure, and contains a resin having a glycidylamine type epoxy unit and an oxetane unit, and a component from a cationic polymerization initiator. The proportion of the glycidylamine type epoxy unit in the resin is more than 10% by mass. If necessary, the cured product contains other components.

[0228] Hereinafter, the description of the cured product of the present embodiment and the adhesive structure of the present embodiment will be described together. The present invention is not limited to the embodiments described below, but may be other embodiments, and within the scope that can be expected by those skilled in the art, changes such as addition, change, omission, etc. may be made. As long as these deformation modes can bring into play the effect of the present invention, they are all included in the scope of the present invention.

[0229] Since the adhesive structure has the above-mentioned constitution, the adhesive performance of the adhesive structure is excellent in terms of adhesiveness, heat resistance and softness. In particular, if the adhesive structure is used to bond two adhesive objects to each other and the two adhesive objects have different linear expansion coefficients, the adhesive structure has the advantage that even when the adhesive structure is used to bond parts that generate thermal stress due to thermal cycles or parts used in high temperature environments above 100°C, it is unlikely that bonding and connection failure will occur. In addition, even when the adhesive structure is formed into a film, the adhesive structure has excellent adhesiveness, heat resistance and softness.

[0230] The adhesive structure comprises a resin having epoxy units of the glycidylamine type and oxetane units.

[0231] The glycidylamine epoxy unit is a cured product obtained by curing the glycidylamine epoxy compound in the adhesive structure-forming curable composition. The oxetane unit is a cured product obtained by curing the oxetane compound in the adhesive structure-forming curable composition. Therefore, the resin containing the glycidylamine epoxy unit and the oxetane unit is a cured product cured by cationic polymerization of the glycidylamine epoxy compound and the oxetane compound.

[0232] The cured product of the glycidylamine epoxy compound is obtained by ring-opening the epoxy group of the glycidylamine epoxy compound using a cationic polymerization initiator, polymerizing and crosslinking the ring-opened epoxy group. An example of a scheme of the curing reaction of the epoxy compound using a cationic polymerization initiator is shown below.

[0233] [Chemical formula 16]

[0234]

[0235] The proportion of the glycidylamine epoxy unit in the resin is not particularly limited and can be appropriately selected according to the purpose, but is preferably 10% by mass or more, more preferably 10% by mass or more and 40% by mass or less, and more preferably 15% by mass or more and 30% by mass or less. When the proportion of the glycidylamine epoxy unit in the resin is 10% by mass or more, the heat resistance and adhesion of the adhesive structure become good.

[0236] The cured product of the oxetane compound can be obtained by ring-opening, polymerizing, and crosslinking the oxetane group of the oxetane compound using a cationic polymerization initiator. An example of a method of the curing reaction of the oxetane compound using a cationic polymerization initiator is shown below.

[0237] [Chemical formula 17]

[0238]

[0239] The oxetane compound in the curing reaction process of the oxetane compound is a compound represented by the above general formula (3), wherein R 8 Represents ethyl, R 9 Indicates -CH2-OR 5 , R 5 It represents a monovalent organic group.

[0240] The ratio of the oxetane unit in the resin is not particularly limited and can be appropriately selected according to the purpose. However, the ratio of the oxetane unit is preferably 10% by mass or more and 60% by mass or less, more preferably 20% by mass or more and 40% by mass or less. When the ratio of the oxetane unit in the resin is 10% by mass or more, the flexibility of the adhesive structure is good, and when it is 60% by mass or less, the heat resistance and adhesion of the adhesive structure are good.

[0241] In this specification, the component derived from the cationic polymerization initiator refers to the cationic polymerization initiator itself, each ion constituting the salt when the cationic polymerization initiator is a salt, or a chemical structure change after the initiation reaction occurs. For example, if SAN-AID SI-100 (substituted arylalkylsulfide) manufactured by Sanshin Chemical Industry Co., Ltd. Hexafluoroantimonic acid) is used as a cationic polymerization initiator, and the components derived from the cationic polymerization initiator correspond to SAN-AID SI-100 itself, substituted arylalkylsulfide ion, hexafluoroantimonate ion, or a substituted arylalkyl sulfide.

[0242] The ratio of the component derived from the cationic polymerization initiator in the adhesive structure is not particularly limited and can be appropriately selected according to the cationic polymerization initiator and the like.

[0243] The adhesive structure includes a resin containing a glycidylamine epoxy unit and an oxetane unit, and a component derived from a cationic polymerization initiator. The adhesive structure may include only an adhesive portion having adhesiveness, wherein the ratio of the glycidylamine epoxy unit in the resin is more than 10% by mass. However, the adhesive structure preferably includes a pattern adjustment portion in addition to the adhesive portion, and the adhesive structure may also include a heat conduction portion, and if necessary, may also include other components.

[0244] The shape of the adhesive structure can be determined by mapping analysis in the cross-sectional direction and in the planar direction using Fourier transform infrared spectroscopy (FT-IR).

[0245] 《Bonding Department》

[0246] The adhesive portion is a member capable of bonding to an adhesive object. The adhesive portion contains a resin having a glycidylamine epoxy unit and an oxetane unit and a component derived from a cationic polymerization initiator. The proportion of the glycidylamine epoxy compound in the resin is 10% by mass or more.

[0247] The adhesive portion may contain other components contained in the adhesive structure-forming curable composition or a cured product of a monomer component of the other components.

[0248] The elastic modulus of bonding portion (if the adhesive structure only includes bonding portion, then the elastic modulus of the adhesive structure) is not particularly limited, can be appropriately selected according to the purpose. However, the elastic modulus of bonding portion is preferably more than 500MPa and less than 10,000MPa, more preferably more than 500MPa and less than 5000MPa. If the elastic modulus of bonding portion is more than 500MPa, the rigidity of bonding portion is excellent, and if the elastic modulus of bonding portion is less than 10000MPa, the bonding portion is not easy to become brittle, difficult to break.

[0249] For example, the elastic modulus of the adhesive portion can be determined by measuring the indentation elastic modulus using a microhardness tester (eg, FISCHERSCOPE (registered trademark) HM2000 manufactured by Fischer) using a film of the adhesive portion formed on a glass surface and cured.

[0250] The glass transition temperature (Tg) of the adhesive portion (if the adhesive structure includes only the adhesive portion, the glass transition temperature (Tg) of the adhesive structure) is not particularly limited and can be appropriately selected according to the purpose. However, from the viewpoint of heat resistance, the glass transition temperature of the adhesive portion is preferably 80° C. or higher. If the glass transition temperature (Tg) of the adhesive portion is 80° C. or higher, the adhesiveness in a high temperature environment is excellent.

[0251] For example, the glass transition temperature (Tg) of the bonding portion can be measured as follows. The curable composition for forming the adhesive structure is injected between two glass plates. Subsequently, the glass plates are heated to cure the curable composition. Then, the cured product is peeled off from the glass, a sample is made, and the glass transition temperature is measured under the following measurement conditions using a rheometer (TA Instruments, ARES-G2).

[0252] [Measurement conditions]

[0253] -Measurement method: Torsional vibration

[0254] -Test sample set: Tensile force: 10gf (gap variable: initial value about 10mm)

[0255] -Strain condition: minimum torque 0.3g·cm (variable strain: initial value 0.05%, maximum value 1%)

[0256] - Temperature: 25℃ to 300℃, 20℃ / min

[0257] - Sample shape: about 20mm×5mm (thickness: 100μm)

[0258] -Objects to be bonded-

[0259] The bonding object is not particularly limited and can be appropriately selected according to the purpose. The bonding object is not particularly limited, and examples thereof include a heat generating member, a cooling member, a substrate, and an electrode.

[0260] The heating component is not particularly limited and can be appropriately selected according to the purpose. As the heating component, for example, semiconductors (chips), semiconductor packages (IC chips), batteries, LEDs, capacitors, resistors, diodes, etc. can be cited, but are not limited to these. Among them, as the heating component, semiconductors or semiconductor packages (IC chips) are preferred. With the high integration and high speed in recent years, it is preferred to have heat resistance with high reliability in the bonding and connection process of the mounting circuit at high temperature.

[0261] The cooling member is not particularly limited and can be appropriately selected according to the purpose. The cooling member is preferably a member that cools the heat of the heat generating member by air cooling, liquid cooling, phase change cooling, thermoelectric cooling, etc. Specific examples of the cooling member include, but are not limited to, a radiator, a heat pipe, a microchannel, a Peltier assembly, a heat sink, a radiator, etc.

[0262] The substrate is not particularly limited and can be appropriately selected according to the purpose. As the substrate, PCB / PWB / BGA substrates (ceramic substrates such as epoxy glass substrates, alumina substrates, copper substrates, polyimide substrates, etc.), lead frames, etc. can be listed, but are not limited to these.

[0263] The electrode is not particularly limited and can be appropriately selected according to the purpose. Examples of the electrode include metals such as Au, Ag, Pd, Cu, Ni, Pt, Fe, and Co, and solder materials such as Sn / Pb and Sn / Ag / Cu, but are not limited thereto.

[0264] 《Pattern Adjustment Department》

[0265] The pattern adjustment part is a member for adjusting and controlling the shape of the coating pattern of the adhesive part. The pattern adjustment part preferably contains a photocurable resin.

[0266] Since the adhesive structure has the pattern adjustment portion, the wetting, spreading and thickness of the adhesive structure-forming curable composition for forming the adhesive portion can be controlled, and the accuracy of forming the adhesive portion by pattern formation can be improved.

[0267] The shape of the pattern adjustment portion is not particularly limited as long as it can adjust and control the shape of the coating pattern of the adhesive portion. However, in order to control the wetting, spreading and thickness of the adhesive structure-forming curable composition used to form the adhesive portion, the pattern adjustment portion is preferably formed on the periphery of the adhesive portion (in the form of an outer frame formed in the shape of the adhesive portion), but can also be formed inside the adhesive portion (in the thickness direction and / or in the plane direction).

[0268] The volume of the pattern adjustment part in the adhesive structure is not particularly limited and can be appropriately selected according to the purpose, but is preferably less than 50 volume % of the volume of the adhesive part. By making the volume of the pattern adjustment part less than 50 volume % of the volume of the adhesive part, the adhesion of the adhesive structure can be easily maintained.

[0269] In addition, it is preferable that the pattern adjustment portion is formed as a low elastic portion that suppresses thermal deformation stress. Here, the low elastic portion means that the elastic modulus is smaller than that of the above-mentioned adhesive portion.

[0270] When the pattern adjustment portion is a low elastic portion, the elastic modulus of the pattern adjustment portion is not particularly limited as long as the elastic modulus is smaller than that of the above-mentioned bonding portion, and can be appropriately selected according to the purpose. However, the elastic modulus of the pattern adjustment portion is preferably 80% or less of the elastic modulus of the bonding portion, and more preferably 50% or less of the elastic modulus of the bonding portion. Specifically, in the case where the pattern adjustment portion is a low elastic portion, the elastic modulus of the pattern adjustment portion is preferably 3000 MPa or less, and more preferably 2000 MPa or less. If the elastic modulus of the pattern adjustment portion is smaller, the stress relaxation effect increases.

[0271] For example, the elastic modulus of the pattern adjustment portion can be determined by measuring the indentation elastic modulus using a microhardness tester (e.g., FISCHERSCOPE (registered trademark) HM2000 manufactured by Fischer Instruments) using a film of the pattern adjustment portion obtained by forming the film on a glass surface and curing the film.

[0272] 《Heat Transfer Department》

[0273] The heat conducting part is a member formed continuously in the thickness direction of the adhesive structure. The heat conducting part has the function of conducting heat in the thickness direction. Therefore, if the heat conducting part is formed by patterning in the adhesive structure, the thermal conductivity, heat dissipation and electrical conductivity between the top and bottom of the adhesive structure in the thickness direction can be improved.

[0274] Therefore, if the adhesive structure is used to adhere a heat generating component, a cooling component, an electrode, or the like, the adhesive structure preferably includes a heat conducting portion.

[0275] The outer shape of the heat conducting part surrounded by the bonding part and / or the pattern adjusting part is not particularly limited and can be appropriately selected according to the purpose. Examples of the outer shape include a combination of straight lines, circular arcs, elliptical arcs, etc., but are not limited thereto.

[0276] In the adhesive structure, the shape and size of the heat-conductive portion exposed on one surface may be the same as or different from the shape and size of the heat-conductive portion exposed on the other surface.

[0277] The thickness of the heat conducting portion is set substantially to be the same as the thickness of the bonding portion and the pattern adjustment portion, and the area (volume) of the heat conducting portion is set to an optimum value according to heat dissipation design.

[0278] If carbon nanoparticle ink or graphene ink is used as the carbon material to form the coating layer, the thickness of the heat conducting portion is preferably 1 μm or more and 300 μm or less.

[0279] If the ceramic material is used as a ceramic paste obtained by mixing ceramic particles and a resin, and a coating layer of the ceramic paste is formed, the thickness of the heat conducting portion is preferably 1 μm or more and 500 μm or less.

[0280] The shape of the adhesive structure is not particularly limited and may be appropriately selected depending on the purpose, and may be in the form of a layer or a block.

[0281] In this specification, the term "layered" means a thickness of 1,000 μm or less, and "block-shaped" means a thickness of more than 1,000 μm. These shapes can be appropriately selected according to the intended use form. For example, in the bonding of a semiconductor (chip) that requires thin filming and various materials bonded to the semiconductor (chip), a layered adhesive structure can be preferably used.

[0282] When the adhesive structure is layered, its thickness is less than 1000 μm, but preferably more than 1 μm and less than 500 μm. From the perspective of thinning requirements and reducing thermal resistance, it is more preferably more than 1 μm and less than 50 μm. From the perspective of heat dissipation, the thickness of the adhesive structure is further preferably more than 1 μm and less than 30 μm, and particularly preferably more than 1 μm and less than 20 μm. If the thickness of the adhesive structure is more than 1 μm and less than 30 μm, when the adhesive structure is used to bond a heat-generating component (e.g., a semiconductor), the heat dissipation of the heat-generating component is improved, and the thickness of the semiconductor device can be reduced.

[0283] The thickness of the adhesive structure can be measured using a probe meter (Alpha-Step D-500, manufactured by KLA-Tenchore), an optical reflectometer (manufactured by F50 Fill Metrics), etc. In addition, in this specification, the term "thickness" refers to the "average thickness" obtained by measuring any three locations using the probe meter and calculating the average value.

[0284] The method for producing the pressure-sensitive adhesive structure is not particularly limited, but the pressure-sensitive adhesive structure is preferably produced by the method for producing a pressure-sensitive adhesive structure of the present embodiment.

[0285] Next, the adhesive structure of the present embodiment will be described in detail with reference to the drawings, but the adhesive structure of the present embodiment is not limited thereto.

[0286] As described above, the adhesive structure comprises a resin containing a glycidylamine type epoxy unit and an oxetane unit, and a component derived from a cationic polymerization initiator. In addition, the adhesive structure comprises an adhesive portion 1, wherein the proportion of the glycidylamine type epoxy unit in the resin is 10% by mass or more. In addition, the adhesive structure may further comprise a pattern adjustment portion 2 that assists in the pattern formation of the adhesive portion 1 and a heat conduction portion 3 that is continuously formed in the thickness direction of the adhesive portion 1.

[0287] Figure 1A It is a schematic cross-sectional view in the film thickness direction of the first example of the adhesive structure according to the present embodiment (a view in the X direction passing through the center of the Y axis in the schematic plan view). Figure 1BIt is a schematic plan view (top view) of the first example of the adhesive structure of the present embodiment. In the accompanying drawings, the vertical direction is the Y axis and the horizontal direction is the X axis. The adhesive layer 10 of the present embodiment is formed by a bonding portion 1 formed by bonding on the contact surface by thermal curing or photocuring, or by thermal curing and photocuring. The bonding portion 1 includes a resin containing at least a glycidylamine type epoxy unit and an oxetane unit, and a component derived from a cationic polymerization initiator. If photocuring is used, a photocationic polymerization initiator is added to the glycidylamine type epoxy compound and the oxetane compound. If thermal curing is used, a thermal cationic polymerization initiator is added to the glycidylamine type epoxy compound and the oxetane compound. If thermal curing and photocuring are used, a curable composition for forming an adhesive structure is prepared by adding a photocationic polymerization initiator and a thermal cationic polymerization initiator. Next, the curable composition for forming the adhesive structure is applied to the substrate or the heat generating component at a desired thickness, and then the heat generating components or the substrate are bonded to each other, and the curable composition is cured, thereby bonding the heat generating components or the substrate to each other. The adhesive portion 1 contains at least a resin containing a glycidylamine type epoxy unit and an oxetane unit, and a component derived from a cationic polymerization initiator. The proportion of the glycidylamine type epoxy compound in the resin is 10% by mass or more, so that the adhesive function is maintained even at high temperatures, and the adhesive portion 1 has thermal stress (strain) resistance. Figure 1A An example is shown in which a curable composition for forming an adhesive structure is applied to a substrate 300 for a printed wiring board (BGA) in a desired thickness, and then a semiconductor (silicon chip) substrate 200 is adhered to the substrate 300, the curable composition is cured, and the substrate 200 and the substrate 300 are bonded to each other.

[0288] Figure 2A It is a schematic cross-sectional view in the film thickness direction of a second example of the adhesive structure according to the present embodiment (a view in the X direction passing through the center of the Y axis in the schematic plan view). Figure 2B 2 is a schematic plan view (top view) of a second example of the adhesive structure of the present embodiment. In the drawing, the vertical direction is the Y axis and the horizontal direction is the X axis.

[0289] The second example of the adhesive structure is different from the first example of the adhesive structure in that the pattern adjustment portion 2 is formed on the outer peripheral portion of the adhesive surface.

[0290] In the structure of the second example of the adhesive structure, the pattern adjustment portion 2 of the outer portion is formed by photocuring or heat curing, or by photocuring and heat curing, and the adhesive portion 1 cured by heat curing is formed inside the pattern adjustment portion 2. Therefore, the thickness of the adhesive structure can be easily adjusted, and the pattern of the adhesive structure can be easily formed. In the second example of the adhesive structure, as shown in FIG. Figure 2B, an example is shown in which the pattern adjustment portion 2 is formed in a rectangular shape at the outer peripheral end of the adhesive portion 1. However, any shape may be adopted as long as the pattern adjustment portion 2 serves as a wall for adjusting the formation area (pattern) of the adhesive portion 1 or as a wettability control portion.

[0291] Figure 3A It is a schematic cross-sectional view in the film thickness direction of a third example of the adhesive structure according to the present embodiment (a view in the X direction passing through the center of the Y axis in the schematic plan view). Figure 3B It is a schematic plan view (top view) of a third example of the adhesive structure according to the present embodiment.

[0292] The third example of the adhesive structure is different from the second example of the adhesive structure in that the heat conducting portion 3 formed continuously in the thickness direction is formed within the rectangular frame of the pattern adjustment portion 2 in the adhesive portion 1 .

[0293] According to the configuration of the third example of the adhesive structure, a heat dissipation effect can be imparted by forming the heat conductive part 3. If the heat conductive part 3 is formed of a metal material or a carbon material and has electrical conductivity, both a heat dissipation effect and an electrical conductivity effect can be imparted.

[0294] (Method for producing adhesive structure)

[0295] The method for producing the adhesive structure of the present embodiment is not particularly limited as long as the adhesive structure-forming curable composition of the present embodiment is used. However, the method preferably includes a step of applying the curable composition for forming an adhesive structure, and may include other steps if necessary.

[0296] When the adhesive structure includes an adhesive portion formed of the adhesive structure-forming curable composition, a pattern adjustment portion, and a thermally conductive portion, it is preferred to include an adhesive portion forming step, a pattern adjustment portion forming step, and a thermally conductive portion forming step.

[0297] The step of applying the adhesive structure-forming curable composition is performed by the same method as the adhesive portion forming step.

[0298] 《Adhesion forming process》

[0299] The bonding portion forming step is a step of forming a bonding portion that can be bonded to a bonding object. In the bonding portion forming step, it is preferred to use the curable composition for forming the bonding structure of the present embodiment, spray the curable composition for forming the bonding structure from a nozzle, apply it to the bonding object, and perform a polymerization reaction. If the bonding structure includes a pattern adjustment portion, it is preferred to form the bonding portion in a manner adjacent to the pattern adjustment portion. In the bonding portion forming step, a curable composition for forming the bonding structure is used as the ink (bonding portion forming ink) for forming the above-mentioned bonding portion.

[0300] The coating method of the adhesive part is not particularly limited and can be appropriately selected according to the purpose. Various types of printing methods can be used, such as spray coating, nozzle coating, dispenser coating, gravure printing, screen printing, flexographic printing, offset printing, reverse printing and inkjet printing. Wherein, in spray coating, dispenser coating, inkjet printing, a pattern can be formed without using a printing plate, a coating film can be formed in a non-contact manner, therefore, the adhesive part can be directly coated on the formation surface of the adhesive object object, therefore, compared with the method for bonding the adhesive part (adhesive structure) prepared in advance by cutting, the above method is preferred, because a film of the adhesive part (adhesive structure) can be formed, and productivity is high. By using these coating methods, even if the adhesive structure includes a pattern adjustment part or a heat conduction part outside the adhesive part, a desired coating can be applied according to these patterns. In addition, inkjet printing can form a very fine pattern, and a film with excellent uniformity can be formed, therefore, it is particularly preferred as the coating method of the adhesive part.

[0301] When the adhesive portion is formed by discharging the adhesive structure-forming curable composition by inkjet printing, droplets of the adhesive structure-forming curable composition can be overlapped to form a thick film.

[0302] In this case, the curable composition for forming the adhesive structure can be stacked adjacent to any one of the composition for forming the pattern adjustment portion of the pattern adjustment portion described later and the composition for forming the heat conduction portion of the heat conduction portion described later as an adhesive portion, and the composition for forming the pattern adjustment portion and the composition for forming the heat conduction portion are formed before the curable composition for forming the adhesive structure. Or the curable composition for forming the adhesive structure can be alternately dripped with a composition (ink) selected from the composition for forming the pattern adjustment portion and the composition for forming the heat conduction portion, adjacent to the stacking structure. Thus, an adhesive portion having any shape can be formed by pattern formation without the need to form the adhesive portion by photocuring. In addition, since it is not necessary to cure the curable composition for forming the adhesive structure by photocuring, or the required performance of the photocuring is reduced, it is possible to select a material for the curable composition for forming the adhesive structure having the best thermosetting and adhesive properties.

[0303] In order to further improve the pattern accuracy of the bonding part, a method of forming a pattern while photocuring the bonding part can be used. That is, the droplets of the curable composition for forming the above-mentioned adhesive structure are patterned and applied, and before the droplets expand over time, the accuracy of pattern formation can be improved by photocuring. In photocuring, a method of forming a semi-cured state and / or stacking photocurable droplets so that only the outermost droplet surface that becomes the contact surface is not photocured is adopted, so that the adhesion of the bonding surface (outermost droplet surface) during bonding can be maintained.

[0304] In particular, by installing the UV LED array on the inkjet head of the inkjet printing system, the jetted droplets are instantly cured by the UV LED, and a pattern with high precision can be formed. Ink suitable for inkjet printing is discharged from a nozzle with a small diameter, so ink with a low viscosity of about 5 mPa·s or more and 200 mPa·s or less is suitable.

[0305] When forming a pattern by such photocuring, it is preferred that the curable composition for forming an adhesive structure contains both a photocationic polymerization initiator and a thermal cationic polymerization initiator. Thus, when patterning a coating film, the accuracy of pattern formation can be improved by photocuring, and the adhesiveness can be improved by thermal curing after bonding.

[0306] 《Pattern adjustment section forming process》

[0307] The pattern adjustment portion forming step is a step of forming a pattern adjustment portion for adjusting and controlling the coating pattern shape of the adhesive portion.

[0308] In the pattern adjustment portion forming step, the pattern adjustment portion is preferably formed by patterning using a pattern adjustment portion forming composition for forming the pattern adjustment portion. The pattern adjustment portion forming composition is preferably ejected from a nozzle, applied to the bonding object, and polymerized. In addition, the pattern adjustment portion is preferably formed adjacent to the bonding portion.

[0309] The order of performing the pattern adjustment portion forming process is not particularly limited and can be appropriately selected according to the purpose. However, the pattern adjustment portion forming process is preferably performed before the bonding portion forming process. Thus, before the bonding portion forming process, the pattern adjustment portion or a part thereof can be formed by the pattern adjustment portion forming process, and in the bonding portion forming process, the wetting, spread and thickness of the curable composition for bonding structure formation can be appropriately controlled.

[0310] Here, the so-called "pattern formation" (also referred to as "patterned formation") refers to a method of selectively configuring the adhesive portion at a specified position and shape. Therefore, "pattern formation" refers to at least one of the following situations: forming a sparse distribution of the above-mentioned adhesive portion and the above-mentioned pattern adjustment portion in the thickness direction and / or the plane direction (direction substantially perpendicular to the thickness direction) of the adhesive structure; and intentionally (artificially) forming the above-mentioned adhesive portion and the above-mentioned pattern adjustment portion into a desired shape in the adhesive structure. Therefore, the term "pattern formation" does not include an island structure that is unintentionally (naturally) formed into any shape.

[0311] The sea-island structure can be produced by a method for producing an adhesive structure, and the pattern formation can be achieved by a method for producing an adhesive structure.

[0312] The coating method of the pattern adjustment part is not particularly limited, and can be appropriately selected from known methods. As a coating method, it is not particularly limited, and various printing methods such as spin coating, casting, micro gravure coating, rod coating, roller coating, wire rod coating, dip coating, slit coating, capillary coating, inkjet printing, spray coating, nozzle coating, dispenser coating, gravure coating, screen printing, flexographic printing, offset printing, reverse printing, etc. can be cited. Among them, from the aspect of being able to form a pattern without using a printing plate and being able to form a coating film in a non-contact manner, preferably spray coating, dispenser coating, inkjet printing. By these coating methods, the desired coating can be carried out according to the pattern of the pattern adjustment part and the bonding part. In addition, the inkjet printing method can form a very fine pattern, and a film with excellent uniformity can be formed, so it is particularly preferred as the coating method of the pattern adjustment part.

[0313] By using the composition for forming a pattern adjustment portion, good filling properties can be achieved in wiring portions such as wire bonding and flip chips, and pattern coating can be performed to advantageously suppress the generation of bubbles and voids that become the starting point of peeling of the adhesive structure.

[0314] In order to improve the pattern accuracy of the pattern adjustment portion, a method of forming a pattern while photocuring the pattern adjustment portion may be adopted, similarly to the bonding portion forming step.

[0315] That is, the accuracy of pattern formation can be improved by photocuring droplets obtained by applying the adhesive structure-forming curable composition by pattern coating before the droplets spread over time.

[0316] When forming a pattern by such photocuring, it is preferred that the composition for forming the pattern adjustment portion contains both a photopolymerization initiator and a thermal polymerization initiator. Therefore, when forming a coating film by patterning, the accuracy of patterning can be improved by photocuring, and the adhesiveness can be improved by thermal curing after bonding.

[0317] -Pattern adjustment unit forming composition-

[0318] In the pattern adjustment portion forming step, the pattern adjustment portion forming composition is used as ink (pattern adjustment portion forming ink) for forming the pattern adjustment portion.

[0319] The material of the pattern adjustment portion forming composition forming the pattern adjustment portion is not particularly limited. However, from the viewpoint of the adhesion and tightness between the adhesive portion and the pattern adjustment portion, it is preferably the same material as the adhesive structure forming curable composition, and more preferably a monomer containing a photocurable resin.

[0320] A monomer of a photocurable resin may be used alone as a composition for forming a pattern adjustment portion, and the composition may be cured to form the pattern adjustment portion. However, from the perspective of being able to appropriately impart pattern adjustment and adhesiveness, it is preferred that the composition for forming a pattern adjustment portion contain a monomer of a photocurable resin and a monomer of a thermosetting resin, and the composition may be cured to form the pattern adjustment portion.

[0321] Specific examples of materials for the composition for forming the pattern adjustment portion include, but are not limited to, glycidylamine epoxy compounds, oxetane compounds, monomers other than glycidylamine epoxy compounds and oxetane compounds, organosilicon compounds, inorganic particles, resins and / or resin particles, adhesion improvers, cationic polymerization initiators, etc. These substances can be used alone or in combination. As the material for the composition for forming the pattern adjustment portion, the same material as the curable composition for forming the adhesive structure can be used, and therefore, the description is omitted.

[0322] The physical properties such as viscosity of the pattern adjustment section forming composition are the same as those of the adhesive structure forming curable composition, and thus description thereof is omitted.

[0323] The pattern adjustment portion can have a lower elastic modulus than the adhesive portion depending on the material type and compounding ratio of the pattern adjustment portion-forming composition used, and can be a cured product (pattern adjustment portion) having excellent flexibility.

[0324] Specifically, as the type of ink material for the pattern adjustment portion forming composition, it is preferred to use an ink mixed with at least one selected from glycidylamine type epoxy compounds, oxetane compounds, glycidyl ether type epoxy compounds, (meth)acrylate monomers, urethane monomers, resins and / or resin particles.

[0325] Furthermore, in the composition for forming a pattern adjustment unit, the ratio of the oxetane compound, the ratio of the glycidyl ether type epoxy compound, the ratio of the (meth)acrylate monomer, the ratio of the urethane monomer, and the ratio of the resin and / or the resin particles can be higher than those in the curable composition for forming an adhesive structure. Thus, it is possible to easily prepare a composition for forming a pattern adjustment unit whose cured product has lower elasticity than that of the cured product of the curable composition for forming an adhesive structure.

[0326] As the pattern adjustment portion forming composition, a commercially available photocurable or thermocurable inkjet solder resist ink may be used.

[0327] Specific examples of commercially available photocurable and thermocurable inkjet solder resist inks include, but are not limited to, IJSR4000, IJSR9000 (manufactured by Taiyo Ink Co., Ltd.), PR1205, PR1243, PR1258 (manufactured by Soo Chemical Co., Ltd.), SUN-004, SUN-013A, SUN-015, C-202, C-400, E635A, E800D (all manufactured by Sekisui Chemical Co., Ltd.), jSVR (manufactured by Dexerials Co., Ltd.), etc.

[0328] 《Heat conduction part forming process》

[0329] In the heat conduction part forming step, it is preferred to use a heat conduction part forming composition for forming the heat conduction part to pattern the heat conduction part. It is preferred to discharge the heat conduction part forming composition from a nozzle to form a heat conduction part continuous in the thickness direction of the adhesive structure, and then perform a polymerization reaction. It is preferred that the heat conduction part is formed adjacent to at least one of the adhesive part and the pattern adjustment part.

[0330] The order of performing the heat conduction part forming process is not particularly limited and can be appropriately selected according to the purpose. However, in order to improve the pattern accuracy of the heat conduction part, it is preferred that after at least patterning the bonding part of the bonding part forming process and / or the pattern adjustment part of the pattern adjustment part forming process, the heat conduction part forming composition is dripped between the bonding part and / or the pattern adjustment part. Thus, the bonding part and / or the pattern adjustment part formed by high-precision pattern formation can be used to improve the accuracy of pattern coating of the heat conduction part in the heat conduction part forming process.

[0331] -Heat conduction portion forming composition-

[0332] In the heat conduction section forming step, the heat conduction section forming composition is used as ink (heat conduction section forming ink) for forming the heat conduction section.

[0333] The material of the heat conduction section forming composition forming the heat conduction section is not particularly limited and may be appropriately selected according to the purpose, but the material preferably contains a heat conductive material and, if necessary, further contains other components.

[0334] --Thermal Conductive Materials--

[0335] The thermally conductive material is not particularly limited and can be appropriately selected depending on the purpose. Examples of the thermally conductive material include metal materials, carbon, and ceramic materials, but are not limited thereto.

[0336] Examples of the metal material include, but are not limited to, silver (Ag), copper (Cu), gold (Au), and aluminum (Al).

[0337] Examples of ceramic materials include, but are not limited to, silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), aluminum nitride (AlN), and boron nitride (BN).

[0338] These materials may be used alone or in combination. Among them, as the thermal conductive material, metal materials are preferred, and metal nanoparticles are more preferred. Metal materials may also be used as the conductive material.

[0339] The primary average particle size (D50) of the thermally conductive material in the thermally conductive portion-forming composition is not particularly limited and may be appropriately selected depending on the intended purpose, but is preferably 0.01 μm to 100 μm, and more preferably 0.3 μm to 10 μm.

[0340] The primary average particle size (D50) of the thermally conductive material can be measured by a dynamic image analysis method, a dynamic light scattering method (DLS), or the like.

[0341] The primary average particle size (D50) of the metal nanoparticles in the composition for forming the heat conduction part is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.005 μm or more and 1 μm or less, and more preferably 0.005 μm or more and 0.2 μm or less. If the primary average particle size (D50) of the metal nanoparticles is 0.005 μm or more and 1 μm or less, when the adhesive structure is used to bond the heating component or the cooling component, a heat conduction part with high thermal conductivity can be formed, wherein the contact surface between the adhesive structure and the heating component or the cooling component has small unevenness, and the contact surface is flat and formed integrally. The primary average particle size (D50) of the metal nanoparticles is preferably 200 nm or less, so that sintering can be performed by treatment at a relatively low temperature of about 150 ° C.

[0342] Furthermore, if the metal nanoparticles have a small particle size, the film thickness of the heat conduction portion can be reduced, and precise patterning is enabled by inkjet printing coating using a nozzle having a small diameter.

[0343] The primary average particle size (D50) of the metal nanoparticles can be measured by dynamic image analysis, dynamic light scattering (DLS) or the like.

[0344] The ratio of the thermally conductive material (excluding the solvent component) in the thermally conductive portion forming composition is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 15% by mass or more and 100% by mass or less, and more preferably 40% by mass or more and 100% by mass or less, relative to the total mass of the thermally conductive portion forming composition. If the ratio of the thermally conductive material in the thermally conductive portion forming composition is within the range of 15% by mass or more and 100% by mass or less, high thermal conductivity can be obtained.

[0345] The coating method using the carbon material and the coating method using the ceramic paste are not particularly limited and can be appropriately selected according to the purpose. As the coating method, spin coating, casting, micro gravure coating, gravure coating, rod coating, roller coating, wire rod coating, dip coating, slit coating, capillary coating, spray coating, nozzle coating, dispenser coating, gravure printing, screen printing, flexographic printing, offset printing, reverse printing, inkjet printing and other printing methods can be cited, but are not limited to these.

[0346] If the heat conduction section forming composition contains a monomer and a polymerization initiator, the ink can be cured by light or heat after coating.

[0347] If the heat conducting part is formed by inkjet printing, it is preferable to use dispersed ink of metal material, carbon, or ceramic material. By using dispersed ink, the viscosity can be adjusted to an ink viscosity suitable for inkjet discharge.

[0348] The viscosity of the dispersion ink is not particularly limited and may be appropriately selected according to the purpose, but is preferably 5 mPa·s or more and 200 mPa·s so that the viscosity is suitable for inkjet discharge.

[0349] The viscosity of the dispersion ink can be measured by the same method as the method for measuring the viscosity of the adhesive structure-forming curable composition.

[0350] In the dispersion ink, a solvent may be used as the dispersion solvent, or a monomer having a low viscosity may be used as the dispersion solvent. As the material of the dispersion solvent, the same material as the solvent in the adhesive structure-forming curable composition may be used.

[0351] The proportion of the thermally conductive material in the dispersed ink is not particularly limited and can be appropriately selected according to the purpose, but is preferably 15% by mass or more and 80% by mass or less relative to the total amount of the dispersed ink. If the proportion of the thermally conductive material in the dispersed ink is 15% by mass or more, a thermal conductive effect can be easily obtained, and if the proportion of the thermally conductive material is 80% by mass or less, the viscosity can be reduced, and such an ink can be suitably used in an inkjet printing method.

[0352] --Other ingredients--

[0353] The other components in the heat conduction section forming composition are not particularly limited and may be appropriately selected according to the intended purpose. For example, the other components include, but are not limited to, resins, monomers, polymerization initiators, solvents, dispersants, and the like.

[0354] As the resin, the monomer, the polymerization initiator and the solvent, the same materials as those of the adhesive structure-forming curable composition can be used, and the preferred forms are also the same, so the description is omitted. The preferred forms of the solvent and the monomer when used as the dispersion ink are also as described above.

[0355] ---Dispersant---

[0356] The dispersant is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include, but are not limited to, a multifunctional comb-type functional polymer having an ionic group in the main chain and a polyoxyalkylene chain in the side chain, etc. The ionic group functions as an adsorption group on the powder surface, and the side chain imparts control of the solubility of the solvent and a steric repulsion effect.

[0357] Specific examples of the dispersant include, but are not limited to, alkyl mercaptans such as dodecanethiol, polyvinyl pyrrolidone polymers, etc. These may be used alone or in combination with other agents.

[0358] The dispersant can be suitably synthesized or a commercial product can be used. Commercial products of the dispersant include, but are not limited to, MALIALIM (registered trademark), MALIALIM SC (registered trademark), MALIALIM FA (registered trademark), ESLEAM C (registered trademark), ESLEAM MP (registered trademark), ESLEAM AD (registered trademark), ESLEAM 221P (registered trademark) (manufactured by NOF Corporation), etc.

[0359] The content of the other components in the heat conducting portion forming composition is not particularly limited and can be appropriately selected according to the purpose, but the solid content of the resin, the dispersant, the monomer cured product, etc. is preferably 5% by mass or less. Thus, the heat conducting portion can be formed in which the content of the heat conducting material in the heat conducting portion is 95% by mass or more by decomposition or gasification removal during sintering.

[0360] The composition for forming the heat conductive portion can be appropriately prepared, and a commercial product can also be used. When the heat conductive material contains a metal material, in addition to the method of using an ink containing the metal material, a method of reducing and precipitating a metal solution ink can also be used. Generally, silver salt inks are known, and these inks can also be used.

[0361] Examples of commercially available products of the heat conduction section forming composition include those listed in the following Table 1. These may be used alone or in combination with other compositions.

[0362] [Table 1]

[0363]

[0364] 《Other Processes》

[0365] The other steps in the method for producing the adhesive structure are not particularly limited and may be appropriately selected according to the purpose, such as a sintering step.

[0366] -Sintering process-

[0367] The sintering step is a step of sintering the metal nanoparticles after the heat conduction section forming step. Therefore, in the heat conduction section forming step, when the heat conduction section forming composition contains metal nanoparticles, the sintering step is preferably performed.

[0368] The sintering method is not particularly limited and can be appropriately selected from known methods, and examples thereof include methods of sintering using heat or light, etc. In this way, a heat-conducting portion having high thermal conductivity sintered between the metal nanoparticles can be formed.

[0369] The firing step of the heat conduction section forming composition may also serve as a step of thermally curing at least one of the adhesive structure forming curable composition and the pattern adjustment section forming composition, for example, a step of bonding the adhesive structure to an object to be bonded.

[0370] The material composition of the adhesive structure can be analyzed by thermal decomposition gas chromatography mass spectrometry (GC / MS), real-time mass spectrometry (DART-MS).

[0371] (Semiconductor device and method of manufacturing the same)

[0372] The semiconductor device of this embodiment includes a semiconductor, an adhesive layer and a substrate, and may further include other layers such as an intermediate layer, and other components other than the semiconductor such as a heat generating component and a cooling component, etc. The adhesive layer is formed of the adhesive structure of this embodiment.

[0373] Since the semiconductor device includes the adhesive structure of this embodiment, it is excellent in adhesiveness, heat resistance, and flexibility, and can be suitably used in, for example, personal computers, smartphones, wearable devices, flexible devices, and the like.

[0374] The stacking order of the components in the semiconductor device is not particularly limited and may be appropriately selected according to the purpose. The semiconductor, the adhesive layer, and the intermediate layer may each be formed of one layer, or may be formed of a plurality of layers.

[0375] <Adhesive layer>

[0376] It is preferable that the adhesive layer is a die bonding layer formed between the substrate and the semiconductor or between one semiconductor and another semiconductor.

[0377] In general, the linear expansion coefficient of a semiconductor is about 3ppm / K, and the linear expansion coefficient of a substrate generally has a higher value, such as 15ppm / K or more. Therefore, due to thermal stress generated by a manufacturing process such as reflow or a thermal cycle caused by drive heating, poor adhesion or connection of the semiconductor is likely to occur. On the other hand, in the above-mentioned semiconductor device, if the adhesive layer is a chip bonding layer formed between the substrate and the semiconductor, the semiconductor and the substrate have different linear expansion coefficients, so that even when thermal stress occurs due to a thermal cycle or when the semiconductor device is used in a high temperature environment of 100°C or higher, the semiconductor device has the advantage that poor adhesion and connection are less likely to occur. In addition, as a resistance in the reflow process, good adhesion strength can be obtained even in terms of shear adhesion strength (chip shear strength) when the semiconductor device is heated to about 260°C.

[0378] Specifically, when the adhesive object of the adhesive structure is set to a square shape with a length of 5.0 mm, a width of 5.0 mm, and a thickness of 0.4 mm, the die shear strength at 260°C is not particularly limited and can be appropriately selected according to the purpose, but is preferably 40 N or more, and more preferably 50 N or more. The die shear strength of the adhesive structure is preferably 40 N or more because in this case, the adhesive structure has heat resistance and adhesion, and a heat dissipation effect can be given to the adhesive structure.

[0379] Furthermore, when the semiconductor device includes a heat generating component other than the semiconductor and a cooling component, the adhesive layer is preferably a heat dissipation layer formed between the heat generating component and the cooling component.

[0380] <Heat-generating components other than semiconductors>

[0381] The heat generating components other than the semiconductors are not particularly limited and can be appropriately selected according to the purpose. Examples of the heat generating components include, but are not limited to, batteries, LEDs, capacitors, resistors, and diodes.

[0382] <Cooling Components, Substrates, and Electrodes>

[0383] The cooling member, the substrate and the electrode are not particularly limited and may be appropriately selected according to the purpose. Examples thereof include, but are not limited to, the same components as those described as the bonding object.

[0384] <Middle Layer>

[0385] Examples of the intermediate layer include, but are not limited to, a heat diffusion layer that diffuses heat in a planar direction and a surface treatment layer that improves adhesion.

[0386] 《Thermal diffusion layer》

[0387] The heat diffusion layer is an intermediate layer that diffuses heat in a planar direction.

[0388] The material for forming the heat diffusion layer is not particularly limited and can be appropriately selected according to the purpose. However, the material preferably includes a material having good thermal conductivity, such as metal (Ag, Cu, Au, Al, etc.), carbon, ceramic (SiO2, Al2O3, AlN, MgO2, BN, etc.).

[0389] The thickness of the heat diffusion layer is not particularly limited and can be appropriately optimized according to heat dissipation design and the like.

[0390] If a metal material such as the above-mentioned metals (Ag, Cu, Au, Al, etc.) is formed into a film under vacuum, the thickness of the heat diffusion layer is preferably 0.05 μm or more and 10 μm or less.

[0391] When the heat diffusion layer is formed by coating with a carbon material such as carbon nanoparticle ink or graphene ink, the thickness of the heat diffusion layer is preferably 1 μm or more and 300 μm or less.

[0392] When the ceramic material is applied as a ceramic paste obtained by mixing ceramic particles and a resin, the thickness of the thermal diffusion layer is preferably 1 μm to 500 μm.

[0393] The method for forming a film of a metal material under vacuum is not particularly limited and can be appropriately selected according to the purpose. As the method, vacuum evaporation, sputtering, ion plating, chemical vapor deposition (CVD) and the like can be cited, but are not limited to these. Each of these methods can be used alone or in combination with other methods. Among them, sputtering is preferred as a method for forming a film of a metal material in a vacuum because it can form a film at a high speed.

[0394] The wet film-forming method for forming the film of the carbon material and the ceramic material is not particularly limited and can be appropriately selected according to the purpose. The method is not particularly limited, and examples thereof include plating methods.

[0395] The coating method using carbon nanoparticle ink or graphene ink and the coating method using ceramic paste are not particularly limited, and can be appropriately selected according to purpose. As coating method, various printing methods such as spin coating, casting, micro-gravure coating, gravure coating, rod coating, roller coating, wire rod coating, dip coating, slit coating, capillary coating, spray coating, nozzle coating, distributor coating, gravure printing, screen printing, flexographic printing, offset printing, reverse printing, inkjet printing, etc. can be enumerated, but not limited to these.

[0396] 《Surface treatment layer》

[0397] The surface treatment layer is an intermediate layer that improves adhesion.

[0398] The surface treatment layer is formed as a layer that adjusts the wettability or surface energy of the film surface, and is formed as a resin film having a hydrophilic group or a hydrophobic group on the surface thereof.

[0399] The material forming the surface treatment layer is not particularly limited and can be appropriately selected according to the purpose. The material is not particularly limited, and examples thereof include materials having a carboxyl group, an amino group, a ketone group, an OH group, a fluorine group, and a silanol group in a resin structure.

[0400] The material forming the surface treatment layer may be a mixture of inorganic particles such as metals (Ag, Cu, Au, Al, etc.), carbon, ceramics (SiO2, Al2O3, AlN, MgO2, BN, etc.) in addition to the above-mentioned resin materials.

[0401] The thickness of the surface treatment layer is not particularly limited, but is preferably within a range of 0.5 μm to 10 μm.

[0402] The method for forming the surface treatment layer is not particularly limited and can be appropriately selected according to the purpose. For example, it can be formed by applying a mixture of a resin material or an inorganic material mixed with an organic monomer material having at least a reactive group and an initiator, and performing curing treatments such as UV irradiation, heat treatment, and dehydration treatment.

[0403] The coating method of the surface treatment layer is not particularly limited, and examples thereof include spin coating, cast coating, micro-gravure coating, gravure coating, rod coating, roller coating, wire rod coating, dip coating, slit coating, capillary coating, spray coating, nozzle coating, dispenser coating, gravure printing, screen printing, flexographic printing, offset printing, reverse printing, inkjet printing and other printing methods.

[0404] Next, the semiconductor device of the present embodiment will be described in detail with reference to the drawings, but the semiconductor device of the present embodiment is not limited to the configuration.

[0405] As described above, the adhesive structure of the semiconductor device comprises a resin having a glycidylamine type epoxy unit and an oxetane unit, and a component derived from a cationic polymerization initiator. The proportion of the glycidylamine type epoxy unit in the resin is 10% by mass or more. The composition of the adhesive structure is as described above in the "Method for producing an adhesive structure".

[0406] Figure 4 1 is a schematic cross-sectional view showing a structural example 1 of a semiconductor device using an adhesive structure (adhesive layer) according to the present embodiment. Figure 4 In the embodiment, the adhesive layer 10 bonds the heat generating component 30 and the substrate 20. Here, the heat generating component 30 is a semiconductor (chip) or a semiconductor package. The adhesive layer 10 withstands the stress caused by the difference in linear expansion coefficient between the heat generating component 30 and the substrate 20, and maintains adhesion even when the temperature changes.

[0407] Figure 5 It is a schematic cross-sectional view showing a second structural example of a semiconductor device using the adhesive structure (adhesive layer) according to the present embodiment. Figure 5 The difference from Structural Example 1 is that a cooling member 40 is bonded to the adhesive layer 10 instead of the substrate 20. The cooling member 40 is a member that cools the heat of the heat generating member 30 by, for example, air cooling, liquid cooling, phase change cooling, or thermoelectric cooling.

[0408] Fig. 6A and Figure 6B This is a schematic cross-sectional view showing a structural example 3 of a semiconductor device using the adhesive structure (adhesive layer) of the present embodiment. Fig. 6A , Figure 6B The difference from Structural Example 1 is that the other heat generating component 30 - 2 and the heat generating component 30 - 1 are bonded together via an adhesive layer 10 . Fig. 6A and Figure 6B The configuration is effective for stacking heat generating components and reducing the temperature difference between 30-1 and 30-2 to obtain a uniform temperature. Figure 6B The heat generating component is a semiconductor (chip), and wire bonding is performed from the upper surface of the heat generating component 30 - 1 through the wiring portion 60 .

[0409] Fig. 7A and Figure 7B This is a schematic cross-sectional view showing a structural example 4 of a semiconductor device using the adhesive structure (adhesive layer) of the present embodiment. Fig. 7A , Figure 7B The difference from Structural Example 1 is that another heat generating component 30 - 2 is bonded to the heat generating component 30 - 1 via another adhesive layer 10 - 2 , and the heat generating component 30 - 1 is bonded to the substrate 20 via the adhesive layer 10 - 1 . Figure 7B The heat generating component is a semiconductor (chip), and wire bonding is performed from the upper surface of the heat generating component 30 - 1 through the wiring portion 60 .

[0410] Fig. 8A and Figure 8B Structural Example 5 of a semiconductor device using the adhesive structure (adhesive layer) of this embodiment is shown. Fig. 8A The difference from Structural Example 1 is that an intermediate layer 50 is formed between the substrate 20 and the adhesive layer 10 . Figure 8B The difference from Structural Example 1 is that an intermediate layer 50 is formed between the heat generating component 30 and the adhesive layer 10 .

[0411] The intermediate layer 50 may be formed between the adhesive layer 10 and the substrate 20 and / or between the adhesive layer 10 and the heat generating component 40. For example, a heat diffusion layer for diffusing heat in a planar direction or a surface treatment layer for improving adhesion may be formed.

[0412] Fig. 9 It is a schematic cross-sectional view showing a structural example 6 of a semiconductor device using the adhesive structure (adhesive layer) according to the present embodiment. Fig. 9 The difference from Structural Example 1 is that an adhesive layer is formed between the electrode 501 and the electrode 502. Structural Example 6 is effective when the electrodes are insulated from each other or when the electrodes are made conductive. As materials for the electrodes 501 and 502, general electrode materials can be used, and specific examples thereof include but are not limited to Ag, Cu, Au, Al, Ni, Sn, Pb, mixtures of these materials, and carbon materials. The electrode layer can be divided and patterned as a wiring pattern.

[0413] (Adhesive layer for transfer)

[0414] The transfer pressure-sensitive adhesive layer of the present invention has the pressure-sensitive adhesive structure of the present invention in a layered form on a temporary support.

[0415] The details of the adhesive structure of the present invention are the same as those described in the above-mentioned "Adhesive structure and method for producing an adhesive structure", and will not be described again.

[0416] <Temporary support>

[0417] The temporary support is not particularly limited as long as the adhesive structure can be produced on its surface and the effect of the adhesive structure is not impaired, and a known release sheet can be used.

[0418] The release sheet is not particularly limited and can be appropriately selected according to the purpose, for example, kraft paper, glassine paper, high-grade paper, etc.; resin films such as polyethylene, polypropylene (biaxially oriented polypropylene (OPP), uniaxially oriented polypropylene (CPP)), polyethylene terephthalate (PET), etc.; laminated paper formed by laminating the above paper and resin films; a material in which a sealant treatment is applied to one or both sides of the above paper with clay or polyvinyl alcohol, etc. and a release treatment such as silicone resin is applied, etc. These can be used alone or in combination with others.

[0419] The method for forming the layered adhesive structure on a temporary support is not particularly limited, and the adhesive structure can be formed in the same manner as in the method for producing the adhesive structure except that the contact object is replaced by the support.

[0420] The advantage of the transfer adhesive layer is that the adhesive structure is easy to store and transport and has excellent operability. Even if the adhesive structure cannot be directly formed on the contact object, the adhesive structure can be easily formed on the contact object by sticking the transfer adhesive layer to the contact object and peeling off the support.

[0421] Example

[0422] Hereinafter, the present invention will be specifically described by way of preparation examples, embodiments and comparative examples, and the present invention includes but is not limited to these preparation examples and embodiments. In addition, in the following preparation examples, embodiments and comparative examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0423] <Viscosity measurement method>

[0424] In the following preparation examples, a cone-plate type rotational viscometer (VISCOMETER TVE-22L, manufactured by Toki Sangyo Co., Ltd.) was used, a conical rotor (1°34'×R24) was used, the rotation speed was 10 rpm, and the temperature of the constant temperature circulating water was 25°C. The temperature of the circulating water was adjusted using a circulating constant temperature bath (e.g., VISCOMETER VM-150III, manufactured by Toki Sangyo Co., Ltd.). The results are shown in the following Tables 3 to 5.

[0425] <Method for measuring evaporation amount (mass loss)>

[0426] In the following preparation examples, the evaporation amount of each ink was measured by using a differential thermogravimetric simultaneous measurement device (TG / DTA7200, manufactured by Seiko Instruments (SII)) under the following measurement conditions to determine the mass reduction rate at 300° C. The results are shown in Tables 3 to 5 below.

[0427] [Measurement conditions]

[0428] - Heating rate 10°C / min, maximum temperature 520°C, hold at maximum temperature for 5 minutes.

[0429] -Ink volume: 20μL

[0430] - Calculation formula: ink evaporation amount (mass %) = (initial mass - reduced mass) / initial mass × 100

[0431] (Preparation Example 1: Preparation of Ink A-1)

[0432] 15 parts of a glycidylamine epoxy compound (TETRAD-X, manufactured by Mitsubishi Gas Chemical Trading Co., Ltd.), 35 parts of an oxetane compound (ARON OXETANE OXT-221, manufactured by Toagosei Co., Ltd.), 35 parts of a glycidyl ether epoxy compound (HD(D), manufactured by Yokkaichi Chemical Co., Ltd.), 5 parts of a thermal polymerization initiator (SAN-AIDSI-80, manufactured by Sanshin Chemical Industry Co., Ltd.), and 10 parts of inorganic particles (silicon dioxide particles, with a primary average particle size of 0.5 μm, KE-S50, manufactured by Nippon Shokubai Co., Ltd.) are mixed to prepare a thermosetting [Ink A-1].

[0433] The viscosity of [Ink A-1] at 25° C. was 80 mPa·s, which was a viscosity suitable for inkjet printing (200 mPa·s or less).

[0434] (Preparation Examples 2 to 13 and 15 to 17: Preparation of Inks A-2 to A-13 and A-15 to A-17)

[0435] The thermosetting [ink A-2] to [ink A-13] and [ink A-15] to [ink A-17] of Preparation Examples 2 to 13 and 15 to 17 were prepared by the same method as that used in Preparation Example 1, except that the composition and ratio in Preparation Example 1 were changed to the composition and ratio shown in A-2 to A-13 and A-15 to A-17 in the following Tables 3 to 5. The viscosities of [ink A-2] to [ink A-13] and [ink A-15] to [ink A-17] at 25° C. are shown in the following Tables 3 to 5, and except for [ink A-17], the viscosities were suitable for inkjet printing.

[0436] The materials used in Preparation Examples 2 to 13 and 15 to 17 and the viscosity characteristics of these materials are shown in Table 2 below.

[0437] (Preparation Example 14: Preparation of Ink A-14)

[0438] The photocurable and thermosetting [Ink A-14] of Preparation Example 14 was prepared in the same manner as Preparation Example 1, except that the composition and ratio in Preparation Example 1 were changed to the composition and ratio shown in A-14 in Table 5 below. The viscosity of [Ink A-14] at 25° C. is shown in Table 5 below, and this viscosity is suitable for inkjet printing.

[0439] The materials used in Preparation Example 14 and the viscosity characteristics of these materials are shown in Table 2 below.

[0440] (Preparation Examples 18 to 22: Preparation of Inks B-1 to B-5)

[0441] The thermosetting [Ink B-1] to [Ink B-5] of the Preparation Examples 18 to 22 as comparative inks were prepared in the same manner as in Preparation Example 1, except that the composition and ratio in Preparation Example 1 were changed to the composition and ratio shown in B-1 to B-5 in Table 6 below. The viscosities of [Ink B-1] to [Ink B-5] at 25° C. are shown in Table 6 below, and are viscosities suitable for inkjet printing.

[0442] The materials used in Preparation Examples 18 to 22 and the viscosity characteristics of these materials are shown in Table 2 below.

[0443] [Table 2]

[0444]

[0445] The structural formulas of the materials listed in Table 2 are shown below.

[0446] [Chemical formula 18]

[0447]

[0448] [Chemical formula 19]

[0449]

[0450] [Table 3]

[0451]

[0452] [Table 4]

[0453]

[0454] [Table 5]

[0455]

[0456] [Table 6]

[0457]

[0458] In [Ink A-1] to [Ink A-17] containing a glycidylamine epoxy compound, an oxetane compound, and a cationic polymerization initiator, the evaporation amount of the ink (i.e., the ink reduction amount) is less than 5% by mass, which suppresses the evaporation of the ink during thermal curing. On the other hand, in [Ink B-1], [Ink B-2], and [Ink B-5] as comparative inks that do not contain an oxetane compound, the evaporation amount of the ink is large. If the evaporation amount of the ink is large, it is difficult to control the film thickness, and the composition of the non-evaporating component (i.e., the solidified product) changes, making it difficult to use the ink as a thermosetting composition for forming an adhesive structure.

[0459] <Measurement of indentation elastic modulus of cured film>

[0460] [Ink A-1] to [Ink A-17] obtained in Preparation Examples 1 to 22 and [Ink B-1] to [Ink B-5] as comparative inks were cured by the following method, and the indentation elastic modulus of the measurement samples of the cured products was measured by the following method.

[0461] - Preparation of samples for measurement -

[0462] [Ink A-1] to [Ink A-17] obtained in Preparation Examples 1 to 22 and [Ink B-1] to [Ink B-5] as comparative inks were respectively used and distributed and applied on a glass surface having a thickness of 1 mm. Thereafter, a fluororesin (PTFE) tape was bonded to the glass having a thickness of 1 mm so that the PTFE tape contacted the printed surface of the ink. The glass was heated at 100°C for 2 hours, then at 200°C for 1 hour, and then heated and cured at 260°C for 5 minutes. Thereafter, the glass having a thickness of 1 mm to which the PTFE tape was attached was peeled off, and a measurement sample having a cured film having a thickness of 15 μm formed on the surface of the glass having a thickness of 1 mm was prepared. The film thickness of the cured film was adjusted by the amount of ink applied.

[0463] Regarding the photocurable and heat-curable [Ink A-14], before heat curing, it was photocured with UV LED (365 nm) using HONLE LED CUBE100 (manufactured by Honle UV Technology), and then heat cured.

[0464] -Determination of indentation elastic modulus-

[0465] The indentation modulus of the measurement sample prepared by the above method was measured under the following measurement conditions using a microhardness tester (FISCHERSCOPE (registered trademark) HM2000, manufactured by Fischer Instruments). The measurement results of the indentation modulus of each measurement sample are shown in Table 4 below.

[0466] [Measurement conditions]

[0467] -Indenter: Vickers Indenter

[0468] -Maximum load: 10mN

[0469] -Maximum indentation depth: 1μm

[0470] - Loading (unloading) time: 40 seconds

[0471] (Example 1)

[0472] In Example 1, a Figure 1A and Figure 1B Laminated samples of the construction shown.

[0473] A printed wiring board (BGA) substrate as the substrate 300 and a silicon chip substrate as the heat generating component 200 are prepared and bonded together with the adhesive layer 10 to form a laminated sample.

[0474] When forming the adhesive layer 10, an inkjet device (manufactured by Cluster Technology) having a nozzle aperture of 60 μm was used.

[0475] The specific method is as follows:

[0476] <Preparation of laminated sample using adhesive layer>

[0477] -Substrate Preparation-

[0478] A ball grid array (BGA) substrate (hereinafter sometimes referred to as a "BGA substrate") having a length of 10 mm, a width of 10 mm, and a thickness of 0.28 mm and composed of a core material / copper wiring / solder resist was prepared. The linear expansion coefficient of the BGA substrate was 14 ppm / K.

[0479] -design-

[0480] A square adhesive layer forming area with four sides of 5.0 mm was designed at the center of the plane direction of the BGA substrate. The adhesive layer forming area was designed so that the center thereof coincided with the center of the BGA substrate.

[0481] -Formation of Adhesive Section-

[0482] As the ink for forming the adhesive part, [Ink A-1] prepared in Preparation Example 1 was used, and inkjet printing was performed on a square adhesive layer forming area with four sides of 5.0 mm to form the adhesive part. At this time, the droplet amount of [Ink A-1] was controlled so as to obtain an average thickness of 15 μm. Thus, as Figure 1A and Figure 1B As shown, an adhesive layer 10 including an adhesive portion 1 is formed on a BGA substrate.

[0483] -Lamination of substrates-

[0484] Next, a square silicon chip substrate 200 having a length of 5.0 mm, a width of 5.0 mm, and a thickness of 0.4 mm was laminated on the adhesive layer 10 on the side opposite to the side in contact with the BGA substrate 300. Thereafter, the substrate was heated at 100°C for 2 hours, then at 200°C for 1 hour, and then heated and cured at 260°C for 5 minutes to prepare a BGA substrate 300 having a length of 5.0 mm, a width of 5.0 mm, and a thickness of 0.4 mm. Figure 1A and Figure 1B A laminated sample of the structure shown in , in which the adhesive layer of Example 1 is used, in which a BGA substrate 300 and a silicon chip substrate 200 are laminated via an adhesive layer 10. The linear expansion coefficient of the silicon chip substrate is 3.34 ppm / K.

[0485] The average film thickness of the adhesive layer is an average value of the film thickness measured at three arbitrary locations of the adhesive layer using a stylus film thickness meter (ALPHA-STEP D-500 manufactured by KLA-Tenchore Corporation).

[0486] (Examples 2 to 4, 8 to 17)

[0487] Except that [Ink A-1] as the ink for forming the bonding portion in Example 1 is replaced by any one of [Ink A-2] to [Ink A-4], [Ink A-8] to [Ink A-17] shown in Table 7 below, a laminated sample is prepared using the bonding layers of Examples 2 to 4 and 8 to 17 in the same manner as Example 1.

[0488] When forming the adhesive layer 10, an inkjet device (STAGEJET, Tritek) using MH5420 (Ricoh) as an inkjet head was used to apply ink with an ink viscosity of 30 mPa·s or less. An inkjet device (Cluster Technology) with a nozzle aperture of 60 μm was used to apply ink with an ink viscosity of 50 mPa·s or more.

[0489] (Examples 5 to 7)

[0490] The adhesive layers of Examples 5 to 7 were used to prepare laminated samples in the same manner as in Example 1, except that [Ink A-1] used as the ink for forming the adhesive portion in Example 1 was replaced by any one of [Ink A-5] to [Ink A-7] shown in Table 7 below, and the average thickness of 15 μm obtained by controlling the amount of ink droplets in Example 1 was changed to the average thickness shown in Table 7 below obtained by controlling the amount of ink droplets.

[0491] (Example 18)

[0492] In addition to Figure 1A and Figure 1B The adhesive layer consisting of only the adhesive portion 1 of Example 1 shown is changed to Figure 2A and Figure 2B A laminated sample of Example 18 was prepared by the same method as in Example 1 except for the adhesive layer composed of the adhesive part 1 and the pattern adjustment part 2 shown.

[0493] That is, the same BGA substrate and silicon chip substrate as those in Example 1 were used.

[0494] Specifically, a laminated sample was prepared by the same method as in Example 1 except that the “design”, “adhesive portion formation”, and “substrate lamination” of Example 1 were changed as follows, and the “pattern adjustment portion formation” was performed as follows.

[0495] -design-

[0496] like Figure 2BAs shown, in the center of the plane direction of the BGA substrate, a square adhesive layer forming area with four sides of 5.0 mm is designed. It is designed so that the center of the adhesive layer forming area coincides with the center of the BGA substrate. In the adhesive layer forming area, the pattern adjustment portion forming area is designed to have a width of 0.5 mm, which surrounds the square adhesive portion forming area with four sides of 4.0 mm. It is designed so that the center of the adhesive layer forming area coincides with the center of the adhesive portion forming area.

[0497] -Formation of Pattern Adjustment Section-

[0498] In Example 18, the photocurable and thermosetting ink [Ink A-14] prepared in Preparation Example 14 was used as the pattern adjustment ink.

[0499] Using [ink A-14], based on the above design, inkjet printing is performed on the pattern adjustment portion forming area on the BGA substrate. At this time, the amount of droplets of [ink A-14] is controlled to form a pattern adjustment portion with an average thickness of 15μm and a width of 0.5mm. Next, using HONLE LED CUBE 100 (manufactured by Honle UV Technology), the discharged [ink A-14] droplets are photocured with UV LED (365nm) to inhibit the wetting and diffusion of the droplets. Therefore, the volume of the pattern adjustment portion is less than 50% by volume of the volume of the adhesive layer 10.

[0500] -Formation of Adhesive Section-

[0501] Next, as the ink for forming the bonding part, [Ink A-1] prepared in the above-mentioned Preparation Example 1 was used, and based on the above-mentioned design, a square bonding part forming area with four sides of 4.0 mm inside the pattern adjustment part formed on the BGA substrate was inkjet printed to form the bonding part. At this time, the droplet amount of [Ink A-1] was controlled to obtain an average thickness of 15 μm. Thus, as Figure 2A and Figure 2B As shown, an adhesive layer 10 including an adhesive portion 1 and a pattern adjustment portion 2 is formed on a BGA substrate.

[0502] -Lamination of substrates-

[0503] Next, a square silicon chip substrate 200 having a length of 5.0 mm, a width of 5.0 mm, and a thickness of 0.4 mm was laminated on the adhesive layer 10 on the side opposite to the side in contact with the BGA substrate 300. Thereafter, the substrate was heated at 100°C for 2 hours, then at 200°C for 1 hour, and then heated and cured at 260°C for 5 minutes to prepare a BGA substrate 300 having a length of 5.0 mm, a width of 5.0 mm, and a thickness of 0.4 mm. Figure 2A and Figure 2BThe stacked sample of the structure shown, in which the adhesive layer of Example 18 is used, in which the BGA substrate 300 and the silicon chip substrate 200 are stacked via the adhesive layer 10.

[0504] (Example 19)

[0505] The adhesive layer of Example 19 was prepared in the same manner as in Example 18, except that the [Ink A-1] used as the adhesive portion forming ink in Example 18 was changed to the [Ink A-4] prepared in Preparation Example 4, and an inkjet device (STAGEJET, Tritek) equipped with an MH5420 (Ricoh) as an inkjet head was used instead of an inkjet device (Cluster Technology, nozzle aperture 60 μm) as the inkjet device for forming the adhesive layer 10. Figure 2A , Figure 2B Laminated samples of the composition shown.

[0506] (Example 20)

[0507] The adhesive layer of Example 20 was prepared by the same method as in Example 18 except that the ink A-1 as the adhesive portion forming ink of Example 18 was changed to the ink A-6 prepared in Preparation Example 6, and the average thickness of 15 μm obtained by controlling the amount of ink droplets in Example 18 was changed to an average thickness of 20 μm. Figure 2A , Figure 2B The laminated samples of the composition shown had a film thickness of 20 μm.

[0508] (Comparative Example 1)

[0509] The laminated sample of Comparative Example 1 was prepared by the same method as in Example 1, except that the [Ink A-1] used as the ink for forming the bonding portion in Example 1 was changed to the [Ink B-1] prepared in Preparation Example 18 which does not contain a glycidylamine-type epoxy compound and an oxetane compound, and an inkjet device (STAGEJET, Tritek) having an MH5420 (manufactured by Ricoh) as an inkjet head was used instead of an inkjet device (manufactured by Cluster Technology, with a nozzle aperture of 60 μm) as the inkjet device for forming the bonding layer 10.

[0510] (Comparative Example 2)

[0511] The laminated sample of Comparative Example 2 was prepared in the same manner as in Example 1, except that the [Ink A-1] used as the ink for forming the bonding portion in Example 1 was changed to the [Ink B-2] prepared in Preparation Example 19 which does not contain a glycidylamine-type epoxy compound and an oxetane compound, and an inkjet device (STAGEJET, Tritek) having an MH5420 (manufactured by Ricoh) as an inkjet head was used instead of an inkjet device (manufactured by Cluster Technology, with a nozzle aperture of 60 μm) as the inkjet device for forming the bonding layer 10.

[0512] (Comparative Example 3)

[0513] The stacked sample of Comparative Example 3 was prepared by the same method as in Example 1, except that [Ink A-1] used as the ink for forming the bonding portion in Example 1 was changed to [Ink B-3] prepared in Preparation Example 20 that does not contain a glycidylamine-type epoxy compound, and an inkjet device (STAGEJET, Tritek) having an MH5420 (manufactured by Ricoh) as an inkjet head was used instead of an inkjet device (manufactured by Cluster Technology, with a nozzle aperture of 60 μm) as the inkjet device for forming the bonding layer 10.

[0514] (Comparative Example 4)

[0515] A laminated sample of Comparative Example 4 was prepared in the same manner as in Example 1 except that [Ink A-1] used as the adhesive portion forming ink in Example 1 was changed to [Ink B-4] containing 5% of the glycidylamine epoxy compound prepared in Preparation Example 21.

[0516] (Comparative Example 5)

[0517] A laminated sample of Comparative Example 5 was prepared in the same manner as in Example 1, except that [Ink A-1] used as the adhesive portion forming ink in Example 1 was changed to [Ink B-5] containing no oxetane compound prepared in Preparation Example 22.

[0518] <Determination of chip shear strength>

[0519] As an evaluation of the adhesive strength in a heated state of the samples of Examples 1 to 20 and Comparative Examples 1 to 5, a shear strength evaluation (die shear strength evaluation) at 260° C. was performed by the following method.

[0520] The laminated samples of Examples 1 to 20 and Comparative Examples 1 to 5 were heated to 260° C. and evaluated for shear adhesion (die shear strength) using an adhesion tester (Dage 4000, manufactured by Nordson). The measurement conditions were in accordance with JEITA Standard ED-4703K-111. The results are shown in Table 7 below.

[0521] [Table 7]

[0522]

[0523] From the results of Table 7, it can be seen that the chip shear strength of Examples 1 to 20 is more than 50N, confirming good adhesion and heat resistance. On the other hand, in Comparative Examples 1, 2, and 3, the chip shear strength is lower than the lower limit of measurement (6.0N). The chip shear strength of Comparative Example 4 is 30.1N, which is lower than that of the embodiment. In Comparative Example 5, the ink is applied in such a way that the average thickness of the bonding portion is 15μm. However, after the bonding portion is formed (cured), it is found that the average thickness is 5μm, which is much thinner than the thickness of 15μm before curing, and therefore, it is difficult to form the bonding portion according to the design.

[0524] In Table 7, the ratio (mass %) of the glycidylamine epoxy compound and the oxetane compound indicates the ratio in the adhesive structure-forming curable composition for forming the adhesive layer.

[0525] Examples of various aspects of this embodiment include but are not limited to the following:

[0526] <1>

[0527] According to the first aspect, the curable composition for forming an adhesive structure can be discharged by inkjet printing, and the curable composition includes: a glycidylamine type epoxy compound; an oxetane compound; and a cationic polymerization initiator, wherein the proportion of the glycidylamine type epoxy compound in the curable composition is 10% by mass or more.

[0528] <2>

[0529] According to a second aspect, in the adhesive structure-forming curable composition according to the first aspect, a ratio of the oxetane compound in the curable composition is 10% by mass or more and 60% by mass or less.

[0530] <3>

[0531] According to a third aspect, in the adhesive structure-forming curable composition according to the first aspect or the second aspect, a ratio of the cationic polymerization initiator in the curable composition is 1% by mass or more and 10% by mass or less.

[0532] <4>

[0533] According to a fourth aspect, in the adhesive structure-forming curable composition according to any one of the first to third aspects, the glycidylamine-type epoxy compound is trifunctional or higher.

[0534] <5>

[0535] According to a fifth aspect, in the adhesive structure-forming curable composition according to any one of the first to fourth aspects, the viscosity of the curable composition at 25° C. is 200 mPa·s or less.

[0536] <6>

[0537] According to the sixth aspect, in the curable composition for forming an adhesive structure according to any one of the first to fifth aspects, it further includes at least one of inorganic particles having a primary average particle size (D50) of 0.1 μm or more and 5 μm or less and resin particles having a primary average particle size (D50) of 0.1 μm or more and 5 μm or less.

[0538] <7>

[0539] The cured product according to the seventh aspect is obtained by curing the curable composition for forming an adhesive structure according to any one of the first to sixth aspects.

[0540] <8>

[0541] The adhesive structure according to the eighth aspect includes: a resin containing a glycidylamine type epoxy unit and an oxetane unit; and a component derived from a cationic polymerization initiator, wherein the proportion of the glycidylamine type epoxy unit in the resin is 10% by mass or more.

[0542] <9>

[0543] According to a ninth aspect, in the adhesive structure according to the eighth aspect, a ratio of the oxetane unit in the resin is 10% by mass or more and 60% by mass or less.

[0544] <10>

[0545] According to a tenth aspect, in the adhesive structure according to the eighth aspect or the ninth aspect, the adhesive structure has an elastic modulus of 500 MPa or more and 5000 MPa or less.

[0546] <11>

[0547] According to an eleventh aspect, in the adhesive structure according to any one of the eighth to tenth aspects, the adhesive structure has a thickness of 1 μm or more and 30 μm or less.

[0548] <12>

[0549] According to the twelfth aspect, in the adhesive structure according to any one of the eighth to eleventh aspects, it further includes: an adhesive part, including a resin containing the glycidylamine type epoxy unit and the oxetane unit, and a component derived from the cationic polymerization initiator; and a pattern adjustment part, including a photocurable resin.

[0550] <13>

[0551] According to a thirteenth aspect, in the adhesive structure according to the twelfth aspect, the volume of the pattern adjustment portion is 50 volume % or less of the volume of the adhesive structure.

[0552] <14>

[0553] According to a fourteenth aspect, in the adhesive structure according to any one of the eighth to thirteenth aspects, further comprising a heat conducting portion formed continuously in the thickness direction.

[0554] <15>

[0555] According to the fifteenth aspect, in the adhesive structure according to any one of the eighth to fourteenth aspects, the adhesive structure has a chip shear strength of 50N or more at 260°C for an adhesive object having a square shape with a length of 5.0 mm, a width of 5.0 mm and a thickness of 0.4 mm.

[0556] <16>

[0557] A semiconductor device according to a sixteenth aspect includes: a semiconductor; an adhesive layer; and a substrate, wherein the adhesive layer includes the adhesive structure according to any one of the eighth to fifteenth aspects.

[0558] <17>

[0559] According to a seventeenth aspect, in the semiconductor device according to the sixteenth aspect, the adhesive layer is a die bonding layer formed between the substrate and the semiconductor or between one semiconductor and another semiconductor.

[0560] <18>

[0561] According to an eighteenth aspect, in the semiconductor device according to the sixteenth aspect or the seventeenth aspect, the semiconductor device further includes a heat generating component and a cooling component, and the adhesive layer is a heat dissipation layer formed between the heat generating component and the cooling component.

[0562] <19>

[0563] A method for producing an adhesive structure according to a nineteenth aspect includes using the adhesive structure-forming curable composition according to any one of the first to sixth aspects.

[0564] <20>

[0565] According to a twentieth aspect, a method for manufacturing a semiconductor device comprises:

[0566] a pattern adjustment portion forming step of forming a pattern by using a pattern adjustment portion forming composition containing a monomer of a photocurable resin to form a pattern to form a pattern adjustment portion on a substrate; and

[0567] The adhesive section forming step is a step of forming an adhesive section adjacent to the pattern adjustment section by using the curable composition for forming an adhesive structure according to any one of the first to sixth aspects.

[0568] The curable composition for forming an adhesive structure according to any one of the first to sixth aspects, the cured product according to the seventh aspect, the adhesive structure according to any one of the eighth to fifteenth aspects, the semiconductor device according to any one of the sixteenth to eighteenth aspects, the method for manufacturing an adhesive structure according to the nineteenth aspect, and the method for manufacturing a semiconductor device according to the twentieth aspect can solve various previous problems and achieve the purpose of the present invention.

[0569] The above embodiments are illustrative and do not limit the present invention. Therefore, many additional modifications and variations are possible based on the above teachings. For example, within the scope of the present invention, the elements and / or features of different illustrative embodiments can be combined and / or replaced with each other. Any of the above operations can be performed in various other ways, such as in an order different from the above order.

[0570] This application is based on and claims the benefit of priority of Japanese Patent Applications No. 2022-097962 and No. 2023-068473 filed with the Japan Patent Office on June 17, 2022 and April 19, 2023, respectively, the entire contents of which are incorporated herein by reference.

[0571] Reference numerals list

[0572] 1. Adhesion section

[0573] 2Pattern adjustment department

[0574] 3Heat conduction part

[0575] 10 adhesive layer

[0576] 10-1 Adhesive layer

[0577] 10-2 Adhesive layer

[0578] 20 substrates

[0579] 30Heating components

[0580] 30-1 Heating components

[0581] 30-2 Heating components

[0582] 40 Cooling components

[0583] 50 Middle Layer

[0584] 60 Wiring Department

[0585] 200 Silicon chip substrate

[0586] 300 printed circuit board (BGA) substrate

[0587] 501 electrode

[0588] 502 electrode

Claims

1. A curable composition for forming an adhesive structure, which can be discharged by inkjet printing, the curable composition comprising: Glycidylamine type epoxy compounds; Oxetane compounds; as well as Cationic polymerization initiator, The ratio of the glycidylamine epoxy compound in the curable composition is 10% by mass or more.

2. The adhesive structure-forming curable composition according to claim 1, in, The ratio of the oxetane compound in the curable composition is 10% by mass or more and 60% by mass or less.

3. The curable composition for forming an adhesive structure according to claim 1 or 2, in, The ratio of the cationic polymerization initiator in the curable composition is 1% by mass or more and 10% by mass or less.

4. The adhesive structure-forming curable composition according to any one of claims 1 to 3, in, The glycidylamine type epoxy compound is trifunctional or higher functional.

5. The adhesive structure-forming curable composition according to any one of claims 1 to 4, in, The curable composition has a viscosity of 200 mPa·s or less at 25° C.

6. The adhesive structure-forming curable composition according to any one of claims 1 to 5, The present invention further includes at least one of inorganic particles having a primary average particle size (D50) of 0.1 μm or more and 5 μm or less and resin particles having a primary average particle size (D50) of 0.1 μm or more and 5 μm or less.

7. An adhesive structure comprising: Resins containing epoxy units and oxetane units of the glycidylamine type; as well as a component derived from a cationic polymerization initiator, The ratio of the glycidylamine epoxy unit in the resin is 10% by mass or more.

8. The adhesive structure according to claim 7, in, The adhesive structure has an elastic modulus of 500 MPa or more and 5000 MPa or less.

9. The adhesive structure according to claim 7 or 8, in, The adhesive structure has a thickness of 1 μm or more and 30 μm or less.

10. The adhesive structure according to any one of claims 7 to 9, further comprising: an adhesive portion including a resin containing the glycidylamine type epoxy unit and the oxetane unit, and a component derived from the cationic polymerization initiator; as well as The pattern adjustment portion includes a photocurable resin.

11. The adhesive structure according to claim 10, in, The volume of the pattern adjustment portion is 50 volume % or less of the volume of the adhesive structure. 12 . The adhesive structure according to claim 7 , further comprising a heat conducting portion formed continuously in a thickness direction.

13. The adhesive structure according to any one of claims 7 to 12, in, The adhesive structure has a die shear strength of 50 N or more at 260° C. for an adhesive object having a square shape with a length of 5.0 mm, a width of 5.0 mm, and a thickness of 0.4 mm.

14. A semiconductor device comprising: semiconductor; Adhesive layer; as well as substrate, Wherein, the adhesive layer comprises the adhesive structure according to any one of claims 7 to 13.

15. A method for manufacturing an adhesive structure, the method comprising: The adhesive structure-forming curable composition according to any one of claims 1 to 6 is used.

Citation Information

Patent Citations

  • Curable composition for inkjet and inkjet coater

    JP2014237814A

  • Curable resin composition, and method for producing semiconductor device

    JP2018065957A

  • Processing unit

    JP2022097962A

  • Particle image analyzer

    JP2023068473A

Cited By

  • Grinding and polishing sample wafer carrier and grinding and polishing equipment

    CN120190758A